SND1 regulates the androgen signaling axis by stabilizing EIF3B mRNA to facilitate the deterioration of prostate cancer - Ying Li; Chengru Yang; Guoli Cui; Shiliang Gui; Linlin Jia; Yu Chen; Honglin Niu; Hua Xin (Molecular Genetics and Genomics, 2026)

Intrauterine exposure to HBsAg attenuates the immune response to hepatitis B vaccine via the miR-155-5p/MyD88 axis of DCs in mouse pups - Xufeng Cui; Jia Lian; Yangle Sun; Xiaosheng Zhang; Bihong Ke; Xinyuan Mo; Ying Zhang; Tian Yao; Yandi Li; Linying gao; Keke wang; Suping Wang; et al. (Medical Microbiology and Immunology, 2026)

Dual roles of static magnetic field on enhancing sulfamethoxazole biodegradation and preventing antibiotic resistance genes transfer in halotolerant fungal-bacterial sludge treating saline aquaculture wastewater - Zhen-Ying Li; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Yuan Sui (Bioresource Technology, 2026)

Rainfall modulates the divergent responses of bacterial and fungal communities to naphthalene contamination in soil - Yuntao Zhao; Duo Zhang; Xin Wang; Yong Cui; Ying Guo; Wei Su; Chen Hong; Wenxin Li; Mengwan Lin; Yixiang Chen; Haobo Ya; Jiayu Chen; et al. (Applied Soil Ecology, 2026)

Progressive fluorescence amplification of molecular rotors via G-run-length engineering of G-rich DNA scaffolds - Ruo-Yao Cui; Yu-Chao Cao; Yi-Xuan Gu; Ling-Li Zhao; Xu-Yang Shen; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2026)

Long-term nitrogen deposition weakens the CH4 sink capacity, but enhances the CO2 and N2O source potential of the alpine grassland soil - Hang Shi; Xiaoqing Cui; Shikui Dong; Zilong Liu; Ran Zhang; Ke Zhang; Xueqi Li; Yuhao Zhang; Hui Zuo; Fengcai He; Xianqi Zhou; Mingjie Ran; et al. (Agriculture, Ecosystems & Environment, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

In-situ growth of modified Fe/Co bimetallic MOFs on carbon felt for highly efficient electro-Fenton catalysis - Ying Li; Mengmeng Cui; Xinlu Ma; Jinwei Liu; Hua Li (Journal of Water Process Engineering, 2026)

Development of a NIR fluorescent probe HDI based on Zinc-mediated competitive coordination for multidimensional detection of glyphosate in complex systems - Ya-Tong Liu; Xi-Yue Luo; Bu-Xiao Wu; Yi-Wen Cui; Jun-Wen Wang; Ying-Kai Yuan; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2026)

High-performance and stable MgFe-layered double hydroxide catalysts for green synthesis of dimethyl carbonate - Cui Qiao; Yunong Li; Qian Su; Yong Li; Ying Liu; Xiaoling Gao; Zifeng Yang; Yifan Liu (Fuel, 2026)

Alcohol and high-fat diet aggravate colitis-induced liver injury via glucocorticoid/IL-6-SAA1 axis in mice - Mingrui Zhao; Han Li; Xinghua Gao; Huijuan Da; Xun Cui; Dongquan Jing; Qixiang Zhao; Ying Wang; Yanling Guo; Zhenhua Gao; Shentian Zhuang; Qiuhua Cao (Food and Chemical Toxicology, 2026)

Perchlorate exposure in Chinese primary children: Levels, potential health risks, and association with sexual development - Yang Xiang; Cui-Lan Bai; Ting-Ting Xu; Yu-Ling Luan; Liang-Ying Liu; Li-Ning Zhao; Ying Guo (Environmental Pollution, 2026)

Disintegrated halophilic aerobic granular sludge restoration using zinc oxide nanoparticles: synergistic effects of fungal toxicity inhibition and extracellular polymeric substances production - Ya-Nan Mi; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Zhen-Ying Li; Xu-Zhen Liu; Tong Ren (Bioresource Technology, 2026)

Vertical redistribution of iron-bound organic carbon and microbial functional shifts across a mangrove restoration chronosequence: redox-mediated constraints on blue carbon stabilization - Hongcheng Li; Jiantong Liu; Qiuxia Chen; Ying Cui; Xiuzhen Li; Zhongzheng Yan (Marine Pollution Bulletin, 2026)

TBK1 associates with TRIF and TRAF3 related IRF3, IRF7, and type I IFN signaling in large yellow croaker Larimichthys crocea - Ying Li; Wen Qi Zha; Wen Feng Cui; Meng Jia Li; Yan Mi Na Chen; Qiu Ye Huang; Qiao Yun Yang; Ying Jia Shen; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Chirality-dependent catalytic activity of nanozymes for accelerated healing of infected wounds - Ying Lu; Shuaishuai Cui; Yang Zhang; Li Wu; Yujian He (Chemical Engineering Journal, 2026)

Climatic, soil, and rhizosphere fungal drivers of flavonoid composition in Scutellaria baicalensis - Ying Liao; Xiaojian Chen; Xuan Du; Jintao Jia; Yahao Xu; Yi Qiang; Bixin Bai; Langjun Cui; Yulong Li (Applied Soil Ecology, 2026)

Influence of cold-tolerant Lactiplantibacillus plantarum L75 inoculation on fermentation quality, aerobic stability and microbial composition of wrapped oat silage in the alpine region - Ying Liang; Hao Guan; Rina Su; Xinyuan Cui; Guanghao Xia; Zohreh Akhavan Kharazian; Mengya Jia; Qiang Li; Xusheng Guo (Animal Feed Science and Technology, 2026)

Context-dependent responses of soil greenhouse gases to grassland restoration: A global meta-analysis - Yu Zhang; Xiaoqing Cui; Hang Shi; Zilong Liu; Ying Li; Zuyan Ma; Shikui Dong (Plant and Soil, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Icaridin-loaded copper(II) chloride-cyclodextrin metal-organic framework for jellyfish repellency - Muzi Yang; Yuxiao He; Qiuming Zhou; Shiyu Zheng; Feng Li; Siying Yang; Ying Cui; Li Wu; Yue Wang; Liang Fang; Jiwen Zhang; Liang Xiao (Journal of Environmental Chemical Engineering, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Regulating spin states via building asymmetric CoTe dual-atom pairs for efficient bifunctional oxygen electrocatalysis in zinc-air batteries - Sichen Huo; Yanjie Chen; Xinyu Wang; Hang Yue; Wenjing Cui; Shuang Shi; Huanyu Guan; Zhuang Cai; Li Li; Ying Dai; Jinlong Zou (Chemical Engineering Journal, 2026)

Starch coating on low-sodium salt via fluidized bed granulation: Sensory improvement and health benefits - Xinyu Song; Xing Li; Xiangyu Liu; Zhaoxiang Ma; Zhi Fan; Zhiqiang Cui; Hui Xiong; Zhixin Li; Ying Zhou; Mingchun Lv; Yuan Li (Carbohydrate Polymers, 2026)

RNA-binding protein TARDBP enhances NPTX1 stability to induce neuronal injury and diabetic cognitive impairment - GuiTing Liu; XiaoXuan Qi; SiOu Li; XinPing Wang; TingYuan Han; LingJia Cui; HuiYing Yue; Feng Liu; Ying Lin (Molecular & Cellular Toxicology, 2026)

An improved Hoerl-Kennard-based ridge estimation method for SBAS-InSAR deformation model resolution - Zhiwei Wang; Xiang Wang; Wenzhuang Ding; Fangfang Li; Ying Cui; Tengfei Gao; Wanqiu Li; Min Zhai (International Journal of Remote Sensing, 2026)

Decalin derivatives from an endophytic fungus Trichoderma harzianum GLQ03 and their anti-inflammatory activities - Pei-Shan Li; Qi-Yu Chen; Jian-Ying He; Xin-Huan Qiu; Feng Wang; Qi Luo; Hong-Hua Cui (Natural Product Research, 2026)

Plant-derived CTLA-4-targeting miR152 via lipid nanoparticles potentiates doxorubicin efficacy in breast cancer immunochemotherapy - Hanyi Ye; Wei Jin; Yifan Feng; Ze Wu; Shuhui Sun; Mengyao Cui; Shun Lv; Bing Jin; Chang Liu; Siming Wang; Ying Li; Zhengqi Dong (Science China Life Sciences, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

Scale effects on motion responses and flow characteristics in moonpool of a semi-submersible platform based on CFD - Ying Li; Tenghui Cui; Dongxu Xie; Hui Yang; Huailiang Li (Ocean Engineering, 2026)

Deconstructing thermal processing of cooperage oak: How oak species, toasting levels and charring levels collectively modulate phenolic profiles - Yongce Huang; Jiamin Gou; Dongsheng Cui; Min Luo; Mengyao Qi; Jin Li; Jisheng Fang; Kunqi Gao; Keji Yu; Changqing Duan; Ying Shi; Yibin Lan (Food Research International, 2026)

Enhanced tolerance of triploid Betula pendula ‘Purple Rain’ to short-term chilling stress is associated with antioxidant capacity and BpSOD gene expression - Jie Zhang; Jingnan Li; Shicheng Li; Ling Lin; Long Liu; Xiaoyue Zhang; Ying Cui; Yujun Zhou; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Experimental investigation of pile anchors in sand under inclined cyclic loading for TLP supported floating offshore wind turbines - Jianbin Cui; Youhu Zhang; Shuzhao Li; Da Li; Ying Huang; Guodong Sun (Ocean Engineering, 2026)

In situ reduction and recovery of Rh(III) from low-concentration solutions using iron-electrocoagulation flocs - Guofu Dai; Chao Peng; Chen Wang; Ying Cui; Song Wen; Jie Jiang; Chenlong Duan; Peng Li (Minerals Engineering, 2026)

High-rate partial nitritation of high ammonia permeate from anaerobic membrane reactor treating food waste: Kinetics, enriched Nitrosomonas and enhanced tolerance to free ammonia and free nitrous acid - Ying Song; Wenzhao Zhao; Shen Cui; Qian Li; Yu Qin; Yuanfan Zhang; Meizhen Wang; Yu-You Li (Journal of Water Process Engineering, 2026)

Earliest centripetal flaking system in eastern Eurasia reveals human behavioral complexity in late Middle Pleistocene China - Yu-chao Zhao; Zhan-yang Li; Hai-wei Zhang; Xin-ya Shao; Hao-hong Cai; Ying Cui; Ya-Nan Li; Hai Cheng; Zhe Hou; Christopher J. Bae; Brian A. Stewart (Journal of Human Evolution, 2026)

Dual-topology helical architectures enable exceptional reusable energy absorption and large recoverable strain in shape memory alloy metamaterials - Meng Zhou; Haohang Li; Ying Yang; Xiang Li; Helong Liu; Jie Chen; Shuke Huang; Yonglin Tan; Lishan Cui; Shijie Hao (Engineering Structures, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Hydrogenophaga pseudoflava widely distributed in wastewater treatment plants exhibiting heterotrophic nitrification-aerobic denitrification: From characterization to genomics - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Jia-Ying Li; Ya-Nan Mi; Xin-Yu Gu (Bioresource Technology, 2026)

Integrating elite selection and micropropagation: a production line for early-stage domestication of Vaccinium bracteatum - Chuizheng Xia; Muhammad Junaid Rao; Ying Wu; Yuanyuan Li; Xuefeng Wang; Weicong Hong; Mengxue Wang; Yihong Jin; Jiani Zhu; Xuan Yu; Haidi Yuan; Jiao Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

From protein-like to humic-like substances: Feed-derived regulation of dissolved organic matter transformation in RAS - Ying Bai; Ruijie Ma; Zhengguo Cui; Hao Li; Hongwu Cui; Yong Xu; Jianlei Chen; Keming Qu (Aquacultural Engineering, 2026)

The Roles of SOCS in Teleost Immunity: Cytokine Regulation and Host Defense - Ying Zhang; Li Yang; Xiuying Cui; Feng Gao; Yanjing Zhao; Xianghui Kong (Reviews in Aquaculture, 2026)
The Suppressor of Cytokine Signaling (SOCS) family comprises key regulatory molecules which are essential for maintaining immune homeostasis in vertebrates. Owing to a teleost‐specific whole‐genome duplication event, SOCS family members exhibit higher diversity and significant functional differentiation, forming a complex and precise immune regulatory network. This review comprehensively summarizes the current understanding of SOCS‐mediated cytokine regulation and host defense mechanisms in teleosts. SOCS proteins, particularly SOCS1 and SOCS3, exert dual regulatory effects in antiviral and antibacterial immunity as well as in inflammatory balance by negatively modulating key pathways such as JAK/STAT and NF‐κB, exemplifying their “double‐edged sword” role. Moreover, we provide the first comprehensive synthesis of environmental regulation of SOCS expression in teleosts, integrating emerging evidence on how to modulate SOCS levels after temperature stress, neuroendocrine activation via cortisol, hypoxia, and chemical pollutants and how to link environmental conditions to immune competence. This environmental perspective supplies direct implications for understanding stress‐induced immunosuppression in aquaculture. Finally, we discuss the potential application of targeting SOCS signaling in aquaculture practices, including applications in disease‐resistant breeding, vaccine development, and immunostimulant design. In‐depth understanding of SOCS diversity and function in fish will provide novel molecular insights and innovative strategies for precise disease control and sustainable aquaculture.

miR-141-5p positively regulates ACVRL1 expression to promote cervical cancer progression - Jianbing Liu; Yongzhi Jiao; Jinjuan Wang; Xiaohua Cui; Ying Gao; Yan Zhang; Jing Xu; Jianqing Hao; Yongli Hou; Wei Wang; Guang Yang; Li Li (Human Cell, 2026)

Two new abietane-type diterpenoids from the roots of Tripterygium wilfordii Hook.f. and their diacylglycerol acyltransferase activity - Hao Xu; Xue-Feng Wu; Ying-Xiao Xiao; Yuan Gao; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Natural Product Research, 2026)

Oxygen supply models shape spatiotemporal distribution of total and active bacterial communities in seawater constructed wetlands - Wenli Liu; Qiufen Li; Ying Ma; Bo Sun; Xianzhe Gong; Zhengguo Cui (Journal of Water Process Engineering, 2026)

Ecological lock-in and functional mismatch in abandoned coastal ponds: mechanisms and management implications - Yi'na Li; Yanzi Cai; Junjun Bai; Ying Man; Dongxue Li; Qing Wang; Yujia Zhai; Ping Qi; Tian Xie; Baoshan Cui (Journal of Environmental Management, 2026)

Evidence of microplastics in human lung tissue: Relationship with clinical indicators - Yang Xiang; Cui-Lan Bai; Li Ma; Liang-Ying Liu; Zi-Feng Zhang; Ying Guo (Journal of Environmental Sciences, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

Enhanced Therapeutic Effects of Extracellular Vesicles Targeting MiR-137 Contribute to Functional Recovery by Attenuating Neuronal Injury After Ischemic Stroke - Hui-Xin Zhang; Li-Qing Tao; Yi-Hang Chen; Tian-Yi Jiang; Zhi-Yuan Ye; Wen She; Chang-Ying Chen; Ya-Li Han; Cui Qi; Chong Shen; Jun Gao (Neuroscience Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A new dameselloid trilobite from the Changhia Formation (Cambrian, Drumian) in central Shandong, North China - Guang-Ying Ren; Jin-Liang Yuan; Yi-Fan Wang; Bai-Zheng An; Kai Chen; Xiao-Hui Cui; Jian Gao; Nan Li (Palaeoworld, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Seasonal shifts in phytoplankton community assembly mediated by hydrological connectivity in a sluice-regulated distributary estuarine network—as a case in the Pearl River Estuary - Yanzi Cai; Xia Li; Guogui Chen; Yiliang Xie; Yujia Zhai; Tian Xie; Mingyu Wang; Fang Gao; Meili Feng; Ying Man; Baoshan Cui (Journal of Hydrology, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Unveiling the mechanism: DOM from chemically pretreated corncobs drives denitrification via mediating microbial community succession - Ying Bai; Ruijie Ma; Zhengguo Cui; Hongwu Cui; Weiman Gong; Wei Dong; Hao Li; Yong Xu; Jianlei Chen; Keming Qu (Journal of Environmental Chemical Engineering, 2026)

Synergistic optimization of yield, quality, and nitrogen use efficiency in indica rice: Influence of nitrogen management and C-N metabolism linkages - Hongjin Li; Tao Li; Jianghui Yu; Tianyu Du; Ping Zhang; Jingjing Cui; Zheshu Xu; Ying Zhu; Fangfu Xu; Qun Hu; Guodong Liu; Guangyan Li; et al. (Field Crops Research, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Spatial Network Structure Characteristics and Resilience Evaluation of Urban Ice and Snow Activities in Cold Border Regions: A Case Study of Harbin City, China - Wenhao Du; Weilin Li; Xiaohong Chen; Ying Wang; Jinming Mou; Yi Cui; Han Wu; Xinyu Wang; Donghong Xie; Yujie Zhang (Chinese Geographical Science, 2026)

Numerical Investigation of Micro-Scale Mass Transfer in Stretched and Compressed Kelvin-Cell Packings for Shipboard Carbon Capture - Bohao Wu; Nan Wu; Yongqi Li; Ying Bi; Daan Cui; Haoheng Liu; Chao Chang; Yulong Ji (Journal of Marine Science and Engineering, 2026)
For shipboard CCUS facilities, the integration of chemical absorption columns is constrained by a limited vertical envelope, which motivates packings with axially stretched or compressed Kelvin cells to support compact layout and flow control. This study employs computational fluid dynamics to investigate microscale flow and mass transfer characteristics in Kelvin cells. A comparison among the regular Kelvin cell (RKC), the vertically elongated Kelvin cell (VEKC), and the vertically compressed Kelvin cell (VCKC) indicates that axial stretching and compression modify internal flow distributions and gas–liquid mass transfer during CO2 absorption. The liquid distribution transitions from a film along the struts with localized accumulation at the nodes in RKC to a continuous columnar stream in VEKC, and then to a stable hollow cylindrical liquid film promoted by lateral redistribution in VCKC. VCKC promotes a stable and expanded liquid film, whereas VEKC tends to induce columnar flow. Reducing the cell size and porosity improves mass transfer efficiency, and the liquid load governs mass transfer flux. These findings provide theoretical guidance for the design and optimization of compact packings for process intensification in shipboard carbon-capture applications.

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Comprehensive evaluation on potentiality and key bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Ming-Teng Li; Yuan Sui (Process Safety and Environmental Protection, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Tobacco–rapeseed system with moderate mineral fertiliser promotes yield by synergistically improving bacterial network complexity and soil fertility - Qi Miao; Lu Liu; Chen Wang; Hao Ying; Yingxin Guo; Dexun Wang; Yanxia Hu; Zhenling Cui; Junwei Sun; Junying Li; Jing Tian (European Journal of Agronomy, 2026)

Electrocatalytic degradation of benzohydroxamic acid in the mining beneficiation wastewater via ferrocene-organic framework cathode coupled with oxygen-contact system: Enhanced cycled bimetallic heterogeneous electro-Fenton process - Jiangpeng Fu; Xiaoyu Han; Ying Li; Jiayang Ma; Haoyang Cui; Xin Zhao; Wenzheng Yu (Chemical Engineering Journal, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

The effect of pet dog exposure on gut antibiotic resistome and microbiome of their owners - Wenjing Cui; Yange Cui; Yuqing Hao; Yuan Li; Ying Wang; Fang Liu; Jinzhao Long; Yuefei Jin; Shuaiyin Chen; Guangcai Duan; Haiyan Yang (Journal of Hazardous Materials, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

The protective effects of dipeptides-WY and YW on blueberry anthocyanins and their interaction mechanism analysis - Yuxi Lang; Xu Si; Hui Tan; Jinlong Tian; Zhihuan Zang; Huijun Cui; Dongdong Zhao; Ying He; Liang Wang; Bin Li (Food Bioscience, 2026)

Fatigue behavior and remaining life evaluation of cracked rib-to-deck joints reinforced with inverted U-shaped plates - Ming-zhe Li; Chuang Cui; Qing-hua Zhang; Le-tian Da; Zhen-yu Cheng; Chuan Wei; Feng-kun Cui; Ying-fang Yang (Engineering Structures, 2026)

Iron and platinum alternating active sites for efficient photocatalytic overall water splitting - Yanfei Fan; Yan Liu; Ying Liang; Kang Chen; Qingqing Li; Dongxu Pan; Shiqiu Zhang; Guanwei Cui; Bo Tang (Chemical Engineering Journal, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Long-term intercropping mitigates warming-induced carbon loss via enhancing microbial and substrate resistance - Wei Wang; Yang Wang; Jian-Ming Li; Meng-Ying Li; Peng He; Yongxing Cui; Sheng-Jun Ji; Wen-Ying Wang; Levis Kavagi; Muhammd Ashraf; Yinglong Chen; Matthias C. Rillig; et al. (Soil Biology and Biochemistry, 2026)

Research progress on spike development of wheat - Yi Ding; Ying Zhang; Tengteng Zhang; Dan Zhao; Yufeng Yang; Kaiyue Wang; Ziqi Zheng; Chaoran Wang; Yongpeng Li; Runya Mao; Yifan Ye; Mengxue Li; et al. (Plant Science, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

A systematic pipeline coupling UHPLC-MS/MS with diagnostic ions screening to reveal the impact of oak barrel toasting on hydrolysable tannin profiles in wine - Yongce Huang; Mengyao Qi; Mengqi Ling; Dongsheng Cui; Yiming Zhang; Chen Huang; Ying Shi; Keji Yu; Jiming Li; Shili Ruan; Changqing Duan; Yibin Lan (Food Chemistry, 2026)

Water-tolerant carbanion engineering for efficient, selective, and reversible SO2 capture by multi-functional ionic liquids embedded hyper-crosslinked polymers - Guokai Cui; Yinfeng Chen; Ruina Zhang; Xing Li; Limin Xu; Xiongfei Nie; Ying Zhou; Quanli Ke; Xiaopo Niu; Zekai Zhang; Huayan Liu; Xiangping Zhang; et al. (Chemical Engineering Journal, 2026)

Thiophene-silane coupling agent for enhancing the dispersibility of graphene and its adsorption capacity for Mo(VI) - Junshuo Cui; Shuang Liu; Liangyu Guo; Zhongjun Li; Zuozhen Zhang; Ying Xiong (Journal of Environmental Chemical Engineering, 2025)

Bio-inspired nanocarriers for oral delivery: Applications in intestinal health - Jia Guo; Zijun Wang; Li Huan; Haiying Yang; Shikai Zhang; Ying Xie; Saiqing Xu; Qiutan Cui; Yang Shan; Shenghua Ding (Food Research International, 2025)

Quercetin alleviates ethanol-induced hepatocyte senescence by interacting with glycinamide ribonucleotide transformylase - Chen Huimin; Peng Shufen; Cui Zhaoyu; Liu Jiaxin; Chen Li; Yin Xingzhu; Wu Bangfu; Zhao Ying; Wang Yu; Mo Li; Liang Chanhua; Li Dongyan; et al. (Food Research International, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

Soil extracellular enzyme stoichiometry reveals the nutrient limitations of soil microbial metabolism under precipitation changes in Ningxia desert steppe of China - Jiali Lian; Jing Chen; Cui Han; Ying Zhao; Xueqin Yang; Jianping Li (European Journal of Soil Biology, 2025)

Cone impact penetration in sand: from high-rate granular mechanics to rapid inversion of shear-strength parameters - Liping Ying; Yuqiong Li; Na Li; Zhiyuan Lv; Qinghao Liu; Gaozhan Cui (Computers and Geotechnics, 2025)

Interface-enhanced CO2-to-C2+ electroreduction via magnesium-regulated PVP nanospheres confining Cuδ+ active sites - Haozhong Yuan; Yuan Zhuang; Senyao Meng; Renlong Ma; Kaixuan Wei; Guiwu Lu; Huiting Hu; Xing Zhou; Ying Cui; Tieyin Zhang; Zhixiang Zeng; Tianteng Yu; et al. (Chemical Engineering Journal, 2025)

Capture and release methods of extracellular vesicles based on functional magnetic beads - Zeying Liu; Ziwei Lu; Ying Li; Yichun Fan; Wenwen He; Yali Cui (Chemical Engineering Journal, 2025)

Controllable interfacial engineering for smart one-component epoxy adhesive with multi-trigger on-demand bonding functionality - Zhaoxin Li; Ying Zhao; Tianyang Cui; Yuan Hu; Jinglei Yang (Chemical Engineering Journal, 2025)

Full-enzymatic three-in-one cascade finishing for woolen textiles: anti-felting, low-temperature dyeing and antibacterial processing - Jiaqi Zhang; Leilei Wu; Jun Wang; Li Cui; Ying Liu; Yuanyuan Yu; Qiang Wang; Ping Wang (Bioresource Technology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Dynamics of convergent plate margins: Progress and challenge - Zhong-Hai Li; Yang Wang; Qihua Cui; Hui-Ying Fu; Fengyuan Cui; Pengpeng Huangfu (Science China Earth Sciences, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Topographic differences in EEG microstates: distinguishing juvenile myoclonic epilepsy from frontal lobe epilepsy - Ying Li; Lidao Xu; Yibo Zhao; Mingxian Meng; Yanan Chen; Bin Wang; Beijia Cui; Jin Liu; Jiuyan Han; Na Wang; Ting Zhao; Lei Sun; et al. (Cognitive Neurodynamics, 2025)

Pore-Structure-Controlled Acoustic Characteristics for Predicting Shallow Gas Distribution in Polar Offshore Drilling - Lei Li; Li He; Ying Zhao; Yu Song; Shiming Wei; Guojing Zhu; Qingying Tang; Tiancong Cui (Journal of Marine Science and Engineering, 2025)
Shallow gas drilling in polar seas poses severe geological hazards, particularly unexpected eruptions that threaten platform safety and the marine environment. Accurate prediction of shallow gas occurrence and eruption risk is therefore essential for safe deep-water operations. However, previous studies seldom considered the coupled effects of gas pressure and pore-structure evolution on acoustic wave velocity, leading to deviations in hazard assessment. In this study, laboratory experiments and numerical simulations were conducted to clarify these mechanisms. Results revealed a non-monotonic relationship between porosity and P-wave velocity in shallow gas-bearing sediments: P-wave velocity decreases with increasing porosity at low porosity levels but increases beyond a critical threshold. This is attributed to changes in particle interactions and cementation that enhance the shear modulus. The inflection porosity for shallow gas (78%) highlights the diagnostic role of pore-structure evolution in predicting shallow gas distribution. A mathematical correlation between P-wave velocity and formation pressure was further established, and MP-PIC simulations showed that higher pressure coefficients significantly accelerate eruption rates, with a 0.1 increase in the pressure coefficient raising the instantaneous eruption velocity by 5.27 m3/min. Based on these findings, a quantitative evaluation method was developed to assess shallow gas hazard risk, providing engineering guidance for site selection and real-time risk prediction, and contributing to safer offshore drilling and ecological protection in polar environments.

Design and test of a precision air-suction maize seed-metering device for plot planting based on CFD-DEM coupling - Jiaqi Li; Zishun Huang; Youcong Jiang; Zijian Cui; Meilin Zhang; Ying Zang; Wei Qin (Computers and Electronics in Agriculture, 2025)

Towards sustainable separation of fuel additives - containing azeotrope by energy-saving extractive distillation process - Xiang Wang; Zhifan Chen; Jingyu Yu; Zhenlin Mu; Ying Xu; Yinglong Wang; Zhaoyou Zhu; Peizhe Cui; Guoxuan Li (Process Safety and Environmental Protection, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Safety and recyclability of active polyethylene terephthalate bottles: A comprehensive assessment using non-target screening and visual sensory evaluation - Can Xu; Sheng Chen; Qi-zhi Su; Jinxin Liang; Ying Zeng; Anqi Cui; Hanke Li; Ben Dong; Dan Li; Huai-ning Zhong (Food Chemistry, 2025)

The synergistic effect of double catalysis of TGase-mediated limited deamidation and cross-linking of zein to form multifunctional zein-based film for food preservation - Na Li; Yutong Sheng; Sihan Liao; Jingwen Zhang; Ying Liu; Ping Wang; Li Cui (Food Chemistry, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Magnetic biochar-cored halophilic aerobic granules: Novel strategy for rapid formation and structural stability enhancement - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Zhen-Ying Li; Rui-Chun Yang; Yuan Sui (Bioresource Technology, 2025)

Preparation and optimization of pickering emulsion stabilized by organosilane-modified palygorskite to encapsulate natural colorants for cosmetic application - Peixuan Tan; Hongyan Cui; Chao Jiang; Chunying Jiang; Qiongyi Huang; Jingying Li; Ying Tang; Yongjun Feng (Applied Clay Science, 2025)

A new isoflavone glycoside from the stems of Eclipta prostrata (L.) L. with glycosidase inhibitory activity - Yuan Gao; Ying-Xiao Xiao; Hao Xu; Xue-Feng Wu; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

A novel chemical constituent from the stems of Akebia quinata and its diacylglycerol acyltransferase inhibitory activity - Yuan Gao; Ying-Xiao Xiao; Hao Xu; Xue-Feng Wu; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2025)

Critical review on magnetic biological effects of microorganisms in the field of wastewater treatment: Theory and application - Hui-Juan Yan; You-Wei Cui; Hui-Kai Liang; Zhen-Ying Li (Journal of Environmental Chemical Engineering, 2025)

Effect of oleic acid iodine value on the flotation performance of oleic acid-based collectors for spodumene - Ying Zhang; Ning Sun; Yuhua Wang; Liu Luo; Man Cui; Yu Li (Journal of Environmental Chemical Engineering, 2025)

Vacancy-rich Nd2S3/TiO2 S-scheme heterojunction for boosted photocatalytic tetracycline hydrochloride degradation: Interfacial engineering and mechanism insight - Qiang Wang; Ying Tang; Tiantian Li; Dan Cui; Weixia Yang; Li Zhang; Kezhen Qi; Feng Yu (Journal of Environmental Chemical Engineering, 2025)

Excellent durability and multifunctional textiles with dual-mode evaporative and radiative cooling enabled by in-situ growth of SiO2 and electrostatic network coating - Luxuan Zhang; Bo Xu; Man Zhou; Ying Liu; Ying Zhang; Li Cui; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

Ionic liquids for highly efficient capture C4 alcohol aldehyde isomer VOCs: experimental and molecular mechanisms - Wenxuan Zhao; Ying Xu; Wenna Liu; Xiang Wang; Zhaoyou Zhu; Yinglong Wang; Peizhe Cui; Guoxuan Li (Chemical Engineering Journal, 2025)

Molecular evolution of chloroplast genome in Triumfetta (Grewioideae, Malvaceae) - Rushan Yan; Yujie Zeng; Chengyu Chen; Abdur Rab; Hui Li; Raza Ullah; Madiha Islam; Ying Cui; Mengyang Liu; Xiaoxuan Tian (Planta, 2025)

Microbial diversity outweighs plant diversity in mediating the response of ecosystem multifunctionality to altered precipitation in a desert steppe - Cui Han; Yi Zhang; Xu Luo; Ying Zhao; Xueqin Yang; Jiali Lian; Jianping Li (Plant and Soil, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Recovery of disintegrated halophilic aerobic granular sludge through ferric ion addition: Dual roles in filamentous fungal inhibition and microbial adhesion enhancement - Hui-Kai Liang; You-Wei Cui; Hui-Juan Yan; Zhen-Ying Li (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

The core cellular network modulates immune phenotype switching in hepatitis B - Chuangeng Chen; Ziqi Zhen; Meng Cui; Xiaoli Hu; Lei Yu; Fengxia Zhou; Xiaorong Yu; Dehui Yang; He Wu; Ying Cui; Xiang Li; Xudong Cui; et al. (Science Bulletin, 2025)

CaCl₂+chitosan treatment inhibits softening and quality decline in postharvest raspberry fruit during cold storage by regulating cell wall and antioxidation metabolisms - Huajun Sun; Ying Liu; Fangzheng Cui; Lili Qian; Sijing Zhu; Yue Li (Postharvest Biology and Technology, 2025)

The calmodulin-binding transcriptional activator transcription factor family in foxtail millet (Setaria italica L.): Molecular characterization, codon bias, and evolutionary trajectory - Huilong Chen; Kexin Ji; Yun Bai; Yuxian Li; Ying Liu; Fang Liu; Yutong Cui; Weina Ge; Zhenyi Wang (Plant Gene, 2025)

Dual-functional berberine-magnolol co-assembled nanoparticles inhibit Fusarium graminearum growth and mycotoxin production - Chenguo Li; Wei He; Yao Cui; Shimin Wu; Qing'ao Song; Ying Li; Jimin Guo; Xizhen Ge; Pingfang Tian (Pesticide Biochemistry and Physiology, 2025)

Impact of cationic reagent structure on the performance of combined collectors in spodumene-feldspar flotation system - Ying Zhang; Yuhua Wang; Ning Sun; Haiqiang Feng; Yu Li; Man Cui (Minerals Engineering, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

A salt-tolerant tetracycline degrading fungal strain of Candida palmioleophila: Characterization and degradation pathway - Zhen-Ying Li; You-Wei Cui; Hui-Juan Yan; Hui-Kai Liang; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Energy efficiency improvement of market-dominant air conditioners based on GraPHsep method - Mengdi Cui; Yuzheng Ying; Yuping Gao; Jinbo Li; Baolong Wang (Journal of Cleaner Production, 2025)

Efficiency of microbial fermentation on microbial shifts, enzymatic activity, and transcriptions in black soldier fly larvae during the sugarcane waste conversion - Fareed Uddin Memon; ChiHo Li; Sheraz Ahmad; Ying Cui; Xingbao Feng; Peng Zeng; Farhan Nabi; Zhijun Huang; Gianluca Tettamanti; Ting Chen; Ling Tian (Environmental Pollution, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Carnitine content and its influencing factors in marine animals collected from China’s offshore region and the Northwest Pacific Ocean - Yufeng Gao; Zhengguo Cui; Jianwei Li; Keming Qu; Qingkui Wang; Lanlan He; Xiangtao Liu; Xiner Zhao; Liuyizhi Zhang; Lingxiao Li; Ying Bai; Fangqun Dai; et al. (Acta Oceanologica Sinica, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Determination of potential α-glucosidase inhibitors in Jinxuan black tea based on bioaffinity ultrafiltration combined with UHPLC-Q-Exactive-MS - Guangneng Li; Jianyong Zhang; Hongchun Cui; Ying Gao; Yuliang Deng; Debao Niu; Junfeng Yin (Food Research International, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Soil disturbance induced by urban shield tunnelling in sandy pebble soil considering non-coaxiality and anisotropy - Jian Cui; Zhigang Yao; Tao Yu; Kaichen Ying; Yong Fang; Wanghao Xu; Yufang Zhang; Jian Li; Bo Liu (Tunnelling and Underground Space Technology, 2025)

Tetracycline degradation by a mixed culture of halotolerant fungi-bacteria under static magnetic field: Mechanism and antibiotic resistance genes transfer - Zhen-Ying Li; You-Wei Cui; Hui-Kai Liang; Hui-Juan Yan; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Hydrogeochemical characteristics of geothermal springs along the central section of Altyn Tagh fault: Implications for deep fluid circulation and tectonic activity - Zhaotong Sun; Jing Liu-Zeng; Yanxiu Shao; Wenxin Wang; Xiaocheng Zhou; Maoliang Zhang; Ying Li; Longfei Han; Fengzhen Cui (Geothermics, 2025)

Productivity of saline soils can be improved by integrating soil–crop system management - Qi Miao; Shuaibing Wu; Junchao Li; Jishi Zhang; Yunhong Wang; Gang Wu; Yixiang Sun; Hao Ying; Zhenling Cui (European Journal of Agronomy, 2025)

A novel ultrasound-triggered cardiac patch for targeted nitric oxide delivery to promote angiogenesis and reduce inflammation for the treatment of myocardial infarction - Lingling Xu; Qiaofeng Jin; Yihan Chen; Nan Cui; Ying Bai; Yihui Wang; Wenqu Li; Wenyuan Wang; Lufang Wang; Yali Yang; Li Zhang; Qing Lv; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Scalable solar-driven reforming of alcohol feedstock to H2 using Ni/Zn3In2S6 photocatalyst” [Chem. Eng. J. 513 (2025) 162965] - Denny Gunawan; Tahlia Stern; Jiajun Zhang; Jodie A. Yuwono; Jian Pan; Qiyuan Li; Haolin Yu; Michael Gunawan; Rosalie K. Hocking; Cui Ying Toe; Jason Scott; Rose Amal (Chemical Engineering Journal, 2025)

Identification of alternative splicing transcripts of Dorsal from Procambarus clarkii and their roles in innate immunity - Ying Huang; Rui Shen; Li-Fan Cui; Qian Ren (Aquaculture, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Differential impacts of invasive aquatic plants water lettuce (Pistia stratiotes) and water hyacinth (Eichhornia crassipes) on plankton community dynamics and its ecosystem functionality - Ziyao Shen; Jian Cui; Jinfeng Li; Ying Peng; Jian Li; Zhen Zhang; Andy Chan; Mianrun Chen; Dongrui Yao (Journal of Environmental Management, 2025)

Nitrogen reduction and split application increased grain yield and agronomic nitrogen use efficiency of oilseed flax (Linum usitatissimum. L) by increasing nitrogen status - Ming Wen; Yuhong Gao; Lizhuo Guo; Bin Yan; Peina Lu; Bin Wu; Yifan Wang; Yue Li; Zhengjun Cui; Peng Xu; Haidi Wang; Yuanyuan Cui; et al. (Field Crops Research, 2025)

Microbial response and the crucial function of predominant phyla in Sedum alfredii-mediated remediation of high concentration of multiple heavy metal soils - Han Zhang; Jianglong Cui; Ying Xiong; Guowen Li; Caili Du; Lieyu Zhang (Environmental Pollution, 2025)

Scalable solar-driven reforming of alcohol feedstock to H2 using Ni/Zn3In2S6 photocatalyst - Denny Gunawan; Tahlia Stern; Jiajun Zhang; Jodie A. Yuwono; Jian Pan; Qiyuan Li; Haolin Yu; Michael Gunawan; Rosalie K. Hocking; Cui Ying Toe; Jason Scott; Rose Amal (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Cortical thickness alternation in obsessive-compulsive disorder patients compared with healthy controls - Chunyu Dong; Hao Zheng; Hailong Shen; Yu Wan; Yinghong Xu; Ying Li; Liangliang Ping; Hao Yu; Chuanxin Liu; Jian Cui; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Surface reconstruction via dissolution-reprecipitation of commercial alumina support to improve propane dehydrogenation performance - Haowei Wang; Wen-Cui Li; Ya-Dong Xie; Huan Yang; Ying Ma; An-Hui Lu (Chemical Engineering Journal, 2025)

Frequency influence on freestanding-mode triboelectric nanogenerators - Zhongjie Li; Bingyan Cui; Hengyu Guo; Ying Gong; Chao Yang; Qin Zhang; Xiaofan Li; Yan Peng; Junlei Wang (Chemical Engineering Journal, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

U (uranium)-polymetallic mineral systems in the world: Genetic types, metallogenic settings and ore-forming mechanisms, and perspective for exploration - Deru Xu; Chanjuan Wang; Bin Li; Guoxiang Chi; Cui Yang; Wei Deng; Wenhao Li; Ying Li; Hengsong Zhang; Longfei Luo; Yaoyao Liao; Shaohao Zou; et al. (Science China Earth Sciences, 2025)

Investigating the mechanisms of flucarbazone-sodium resistance in Bromus japonicus Thunb - Yuning Lan; Xinhui Xue; Hailan Cui; Ruolin Wang; Ying Sun; Hongjuan Huang; Shouhui Wei; Xiangju Li; Zhaofeng Huang (Plant and Soil, 2025)

Plant species richness enhances aboveground primary productivity via net biodiversity effects and bacterial community interactions - Xu Luo; Yingzhong Xie; Shaoli Yue; Mingfan Yang; Cui Han; Yaxin Zhao; Ying Zhao; Jianping Li (Applied Soil Ecology, 2025)

Kuenenia-enriched hydroxyapatite granules enable stable high-rate nitrogen removal of high-strength food waste permeate in an EGSB-anammox system: Insights into granule performance and process scalability - Lan Lin; Wenzhao Zhao; Shen Cui; Ying Song; Yuanfan Zhang; Yu-You Li (Journal of Water Process Engineering, 2025)

Fertilization-recruited Actinomycetota enhances nutrient and energy metabolisms to favor plant growth and arsenic accumulation in Pteris vittata - Yong-He Han; Yi-Xi Li; Xi-Wen Cui; Ying Zhu; Hong Zhang; Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Water-induced phase separation ionogel for Recyclable information encryption - Ying Cui; Yunlong Liu; Qian Wang; Shuhong Li; Wenjun Wang; Xiaochen Dong (Chemical Engineering Journal, 2025)

Unraveling microbial community ecology and its effects on function and structure of halophilic aerobic granular sludge under varying salinities - Hui-Juan Yan; You-Wei Cui; Jun Chen; Hui-Kai Liang; Zhen-Ying Li (Bioresource Technology, 2025)

Pathogenic characterization and drug resistance of neonatal sepsis in China: a systematic review and meta-analysis - Ruixue Wu; Xiaoyu Cui; Rui Pan; Na Li; Ying Zhang; Jianbo Shu; Yang Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Climate and human activities shaping carbon-water-food interactions: Implications for governance in the Yangtze River Basin and its sub-basins, China - Yulong Li; Liang Zheng; Hongping Cui; Di Wu; Ying Wang (Journal of Environmental Management, 2025)

Hydrogeochemical characteristics of hot springs in the Longriba fault, northeastern Tibetan Plateau: Tectonic implications for geothermal fluid circulation - Yuwen Wang; Xiaocheng Zhou; Jingchao Li; Yunfei Bai; Yucong Yan; Jiao Tian; Miao He; Zhaojun Zeng; Bingyu Yao; Gaoyuan Xing; Shihan Cui; Ying Li; et al. (Journal of Asian Earth Sciences, 2025)

Maternal green space exposure and congenital heart defects: A population-based study - Shihan Zhen; Lu Zheng; Qian Li; Zhouxin Yin; Hong Cui; Yan Li; Shuqi Wu; Kecheng Li; Ying Zhao; Fengchao Liang; Jiajin Hu (Environmental Research, 2025)

Decoding the end-Devonian Hangenberg oceanic anoxia event: Insights from ironstones in South China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Ying Cui; Rui-Zhong Hu; Zerui Ray Liu; Xiyao Li (Earth and Planetary Science Letters, 2025)

The toxic impacts of microplastics-borne benzo[a]pyrene and heavy metals on the health and behavior of seahorse Hippocampus erectus - Ying Liu; Nan Li; Dongwei Shang; Yanjing Yang; Pei Cui; Jinhui Sun (Journal of Oceanology and Limnology, 2025)

Comamonas squillarum sp. nov., Isolated from Intestine of Red Swamp Crayfish (Procambarus clarkii) - Shi Shi; Dao-Feng Zhang; Hong-Chuan Wang; Fu-Hui Jiang; Li-Fan Cui; Ying Huang (Current Microbiology, 2025)

Ecological risk assessment for BDE-47 in marine environment based on species sensitivity distribution method - Ying Bai; Ruijie Ma; Zhengguo Cui; Liping Liu; Dongsheng Ding; Qingjing Hu; Bin Xia; Zhaochuan Li; Haibo Zhang; Keming Qu (Marine Environmental Research, 2025)

Regional and longitudinal dynamics of human milk protein components assessed by proteome analysis on a fast and robust micro-flow LC–MS/MS system - Junxia Cao; Xinling Cui; Hai Lu; Hui Wang; Wen Ma; Zhan Yue; Kemiao Zhen; Qiaosi Wei; Hongmei Li; Shilong Jiang; Wantao Ying (Food Chemistry, 2025)

The influence of polyphenols on the hydrolysis and formation of volatile esters in wines during aging: An insight of kinetic equilibrium reaction - Mengqi Ling; Dongsheng Cui; Baoqing Zhu; Demei Li; Haibin Mu; Jin Li; Ying Shi; Changqing Duan; Yibin Lan (Food Chemistry, 2025)

Manganese halides with timely and delayed reversible thermal fluorescence quenching for dual-secure information encryption and anti-counterfeiting - Li Cong; Longyun Lv; Ying Liu; Yuxin Jia; Xuerui Chang; Yufan Lin; Juan Li; Bin-Bin Cui (Chemical Engineering Journal, 2025)

Advanced micro-textural engineering for the fabrication of high-performance superomniphobic surfaces - Chang Lv; Tao Wang; Yuanwei Ding; Haiyan Li; Yulong Ying; Lvlv Ji; Weihao Cui; Lei Liu; Sheng Wang (Chemical Engineering Journal, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

Remediation mechanism of high concentrations of multiple heavy metals in contaminated soil by Sedum alfredii and native microorganisms - Zihe Wang; Han Zhang; Ying Xiong; Lieyu Zhang; Jianglong Cui; Guowen Li; Caili Du; Kaiyang Wen (Journal of Environmental Sciences, 2025)

Identification and characterization of 16 tripartite motif-containing proteins from Takifugu obscurus - Li-Fan Cui; Rui Shen; Xiao-Rui Song; Yan Shi; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Dy and K double-additive modified Co3O4 catalyst with high resistance to NO for catalyzing N2O decomposition - Haibiao Yu; Yanan Li; Yan Pan; Yuanting Du; Xiaogeng Feng; Junshuo Cui; Zhenning Lou; Weijun Shan; Ying Xiong (Chemical Engineering Journal, 2025)

Integration of cobalt coordination polymer-based triboelectric nanogenerators as sustainable power sources for self-driven selective photocatalytic reactions - Fei Wang; Ying-Ying Zhang; Shuo Li; Lin Zhang; Yuanmeng Tao; Jiaxing Cui; Dandan Wang; Mingli Jiao; Chao Huang (Chemical Engineering Journal, 2025)

Analysis of nitrogen flow in the Yellow River Basin over a long time series - Ying Cui; Ruiping Li; Xu Chen (Environmental Monitoring and Assessment, 2024)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Carbon availability regulates fungal and bacterial populations in halophilic aerobic granular sludge treating saline wastewater - Hui-Kai Liang; You-Wei Cui; Zhen-Ying Li; Hui-Juan Yan; Xu Wang (Science of The Total Environment, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Vitrification cryo-foil method for shoot tip cryopreservation and virus eradication in apple - Min-Rui Wang; Jun-Hua Bao; Xiao-Yan Ma; Zi-Han Yan; Zhen-Hua Cui; Li-Ying Zhu; Dong Zhang; Qiao-Chun Wang (Cryobiology, 2024)

Lignin-derived compounds assisted with Kocuria marina H-2 and Pseudomonas putida B6-2 co-culture enhanced naphthalene biodegradation - Jia-Qi Cui; Zhi-Qiang He; Kai Chen; Samuel Ntakirutimana; Zhi-Hua Liu; He Bai; Bing-Zhi Li; Ying-Jin Yuan (Bioresource Technology, 2024)

Typical alien invasive aquatic-plant species changed the stability rather than the diversity of plankton community in fresh water - Ziyao Shen; Jian Cui; Jinfeng Li; Ying Peng; Jian Li; Yu Liang; Yang Zhou; Zhen Zhang; Linhe Sun; Dongrui Yao (Science of The Total Environment, 2024)

Comparative quantitative phosphoproteomic and parallel reaction monitoring analysis of soybean roots under aluminum stress identify candidate phosphoproteins involved in aluminum resistance capacity - Ying He; Zhengbiao Wang; Wenmo Cui; Qingxiu Zhang; Meihui Zheng; Wen Li; Jie Gao; Zhenming Yang; Jiangfeng You (Journal of Hazardous Materials, 2024)

Metabolism of nitrogen and sulfamethoxazole, performance recovery mechanism, and antibiotic resistance genes (ARGs) behaviors in membrane aerated biofilm reactor (MABR) - Ting Li; Xiwei Cao; Lijun Gu; Ying Cui; Xinglin Li; Yi Li; Sher Jamal Khan; Baoan Li; Shuo Zhang (Journal of Cleaner Production, 2024)

A time-saving pH-ultrasonic-shifting method for insoluble pea protein isolate to encapsulate polyphenol: Binding mechanism, structure, and functional characteristics - Linrong Yu; Qingchen Cui; Xiaolu Zhang; Liping Zhou; Mengshuang Li; Lei Tian; Xianggen Wu; Ying Jie (Food Hydrocolloids, 2024)

Molecular cloning and functional characterization of eight galectin genes from Takifugu obscurus - Ying Huang; Sheng-Hao Du; Li-Fan Cui; Fu-Hui Jiang; Zhe Zhao (Fish & Shellfish Immunology, 2024)

In situ iron coating of amorphous boron and characterization of its energy release behavior - Hongyang Li; Hong Li; Chao Wang; Zhenfeng Shen; Shentao Zeng; Sujun Shi; Qing Cai; Wenqi Xu; Ran Wang; Cui Luo; Ying Liu (Chemical Engineering Journal, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Advanced design of metal single-atom (Pt, Mn, Fe or Cu) loaded S-Ni(OH)2 nanosheets array catalysts to achieve high-performance overall water splitting - Wenhui Fang; Tingting Tang; Min Li; Shixian Xin; Ying Wu; Yutao Cao; Zhize Yu; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Diffusion behavior and environmental impact of odorants and TVOCs detected in a wastewater treatment plant for collaborative leachate treatment in Northwest China - Zilan Liao; Tong Gao; Pengyu Li; Tianlong Zheng; Lin Li; Cui Li; Wenwen Wang; Ying Wang; Junxin Liu (Chemosphere, 2024)

Hazards of toxic metal(loid)s: Exploring the ecological and health risk in soil–crops systems with long-term sewage sludge application - Shitao Gao; Yanmei Dong; Qingqi Jia; Shuxia Wu; Jiayun Bai; Chao Cui; Ying Li; Peng Zou; Miaoying An; Xinzhong Du; Hongbin Liu (Science of The Total Environment, 2024)

Effects of dissolved organic matter on distribution characteristics of heavy metals and their interactions with microorganisms in soil under long-term exogenous effects - Han Zhang; Wenjie Liu; Ying Xiong; Guowen Li; Jianglong Cui; Chen Zhao; Lieyu Zhang (Science of The Total Environment, 2024)

A positive loop between relish and cuticle proteins and their roles in regulating AMPs expression during bacterial infection in Eriocheir sinensis - Xia Liang; Ying Huang; Hao Xu; Qian Ren; Di Cui; Xin Qi; Hai-Li Zhang (Fish & Shellfish Immunology, 2024)

Advancing the treatment of low carbon-to-nitrogen ratio municipal wastewater using a novel microaerobic sludge bed approach: Insights into enhanced performance and functional microbial community - Wenbo Li; Xiao Zhang; Bowei Zhao; Ying Cui; Philip Antwi; Rui Li; Aijuan Zhou; Jinping Li; Xiuping Yue (Environmental Research, 2024)

Recurrent marine anoxia in the Paleo-Tethys linked to constriction of seaways during the Early Triassic - Yuyang Wu; Alexandre Pohl; Li Tian; Jacopo Dal Corso; Ying Cui; Daoliang Chu; Jinnan Tong; Huyue Song; Hanchen Song; Haijun Song (Earth and Planetary Science Letters, 2024)

Influence of scion cultivar on the rhizosphere microbiome and root exudates of Phaseolus vulgaris in grafting system - Xiuli Wei; Yuanyuan Cui; Jiaqi Wang; Guoyuan Song; Ying Cao; Long Liu; Zhixin Liu; Jing Yang; Chen Li; Jiao Wang; Moran Li; Xiao Xiao (Plant and Soil, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Impact of corticosteroid doses on prognosis of severe and critical COVID-19 patients with Omicron variant infection: a propensity score matching study - Shiyao Wang; Ziying Chen; Xinran Zhang; Xiaojing Wu; Yuqiong Wang; Qi Zhang; Linna Huang; Xiaoyang Cui; Ying Cai; Xu Huang; Jingen Xia; Sichao Gu; et al. (Inflammopharmacology, 2024)
Background There is lack of research on corticosteroid use for severe and critical COVID-19 patients with Omicron variant infection. Methods This multi-center retrospective cohort study involved 1167 patients from 59 ICUs across the mainland of China diagnosed with severe or critical SARS-CoV-2 Omicron variant infection between November 1, 2022, and February 11, 2023. Patients were segregated into two groups based on their corticosteroid treatment—usual dose (equivalent prednisone dose 30–50 mg/day) and higher dose (equivalent prednisone dose > 50 mg/day). The primary outcome was 28-day ICU mortality. Propensity score matching was used to compare outcomes between cohorts. Results After propensity score matching, 520 patients in the usual dose corticosteroid group and 260 patients in the higher dose corticosteroid group were included in the analysis, respectively. The mortality was significantly higher in the higher dose corticosteroid group (67.3%, 175/260) compared to the usual dose group (56.0%, 291/520). Logistic regression showed that higher doses of corticosteroids were significantly associated with increased mortality at 28-day (OR = 1.62,95% CI 1.19–2.21, p = 0.002) and mortality in ICU stay (OR = 1.66,95% CI 1.21–2.28, p = 0.002). Different types of corticosteroids did not affect the effect. Conclusions The study suggests that higher-dose corticosteroids may lead to a poorer prognosis for severe and critical COVID-19 patients with Omicron variant infection in the ICU. Further research is needed to determine the appropriate corticosteroid dosage for these patients.

Evaluation of growth, immune characteristics and gut microbiota of juvenile sea cucumber Apostichopus japonicus fed with fermented feed from Corynebacterium glutamicum - Jiarong Cui; Xiaofei Tan; Zixuan Xu; Xinyu Sun; Liang Wang; Honglei Zhan; Yujia Liu; Ying Li; Bingnan Liu (Aquaculture International, 2024)

Examination of the effects of excess microalgae availability on the disruption of mussel byssus secretion - Ji-Yue Ni; Yan Zhou; Yu-Qing Wang; Shi-Hui Huang; Qian-Wen Cui; Wen-Yi Wang; Xiao-Ying Yang; Deborah M. Power; Yi-Feng Li (Aquaculture, 2024)

The receptor kinase OsANX limits precocious flowering and inflorescence over-branching and maintains pollen tube integrity in rice - Lan-Xin Zhang; Can-Can Shen; Ying-Xue Bai; Hao-Yue Li; Chen-Li Zhu; Chen-Guang Yang; Ammara Latif; Ying Sun; Cui-Xia Pu (Plant Science, 2024)

The impact of a natural resource protection policy on economic development: Based on a policy evaluation of China’s coal resource tax reform - Shuhong Wang; Weiyao Li; Ying Zhang; Malin Song; Xueli Chen; Lianbiao Cui (Energy Policy, 2024)

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Effect of using reclaimed water via furrow and subsurface drip systems under alternate partial root-zone irrigation mechanism on crops growth and soil properties - Mahmoud S. Hashem; Wei Guo; Xue-Bin Qi; Ping Li; Ying-jun She; Jiaxin Cui; Tong Li (Irrigation Science, 2024)
The growing population in the face of water scarcity inevitably necessitates the quest for alternative sources of irrigation water, which integrates them with irrigation strategies for improved agricultural productivity to meet the Sustainable Development Goals. A three-year field experiment was conducted in 2017, 2018, and 2019 to investigate the effect of water quality (reclaimed water (RW) and clean water (CW)), irrigation techniques (subsurface drip irrigation (SDI) and furrow irrigation (FUI)), irrigation methods (full irrigation (FI) and alternate partial root-zone irrigation (APRI) (70% ETc)), and their interactions on the fresh fruit yield (FY), irrigation water use efficiency (IWUE), and nitrogen use efficiency (NUE) of tomatoes. Further, electrical conductivity (EC), pH, and organic matter (OM) of soil were evaluated. The experiments were undertaken over three growing spring seasons in a greenhouse at the Chinese Academy of Agricultural Sciences in Henan Province, China. Throughout the three years of this study, the yield, the IWUE, and the NUE values of all treatments under RW were higher than those corresponding values under CW. The trend was the same under SDI as it was under FUI. Statistical analyses revealed that there was no significant effect ( P > 0.05) of water quality, irrigation technique, and irrigation methods on the soil EC, pH, and OM over the three years. In addition, the interaction between the different experimental factors over the three years of the study was not significant. In conclusion, the application of RW under SDI can result in saving CW and increasing productivity without any negative effect on the investigated soil properties. Furthermore, when RW-SDI is used in conjunction with APRI, it can result in increasing IWUE.

Age-related alterations in vortex veins on indocyanine green angiography - Chen-Xi Cai; Shan-Shan Yu; Xiao-Mei Xiong; Bing-Qian Liu; Zhen-Qiang Lin; Qiang Wang; Jin-Li Cui; Ze-Hao Liu; Tao Li; Lin Lu; Ying Lin (GeroScience, 2024)
To determine age-related alterations in vortex veins in healthy subjects. A total of 228 healthy subjects (aged 4 to 86 years) were recruited and divided into four groups (G1, <21 years; G2, 21–40 years; G3, 41–60 years; and G4, 61–86 years). The clinical characteristics of the participants were recorded, and parameters including the number of vortex vein roots (NVVR), the central vortex vein diameter (CVVD), the mean root area of the vortex vein (MRAVV), and the weighted mean of the thickest branch diameter (WMTBD) were obtained by marking the vortex veins on indocyanine green angiography (ICGA). The NVVR in the age group over 60 years old was significantly lower than that in other age groups ( P < 0.05). The CVVD, MRAVV, and WMTBD of all age groups increased with increasing age ( P < 0.05). The NVVR was unevenly distributed among the quadrants ( P < 0.001). The proportions of type four vortex veins (complete systems including ampulla) and anastomotic branches of the vortex veins were significantly increased in elderly participants over 50 years of age ( P < 0.05). Subfoveal choroidal thickness was significantly correlated with age, NVVR, CVVD and MRAVV ( P < 0.05). This is the first study to reveal age-related alterations in vortex veins on ICGA in a healthy population. Aging may lead to partial vortex occlusion and residual vortex dilation. As age increases, anastomotic branches increasingly appear between the originally independent vortex veins. Translational relevance: Aging may lead to partial vortex occlusion and residual vortex dilation.

PFDA promotes cancer metastasis through macrophage M2 polarization mediated by Wnt/β-catenin signaling - Zhenyan Cui; Zekun Liu; Xiaoyu Yuan; Kean Lu; Mengyao Li; Sinan Xu; Kelie Chen; Fang Zheng; Ying Li; Paul Héroux; Yihua Wu; Dajing Xia (Chemosphere, 2024)

Effect of hydraulic retention time on denitrification performance and microbial communities of solid-phase denitrifying reactors using polycaprolactone/corncob composite - Hongwu Cui; Yuna Feng; Weibin Lu; Lu Wang; Hao Li; Yu Teng; Ying Bai; Keming Qu; Yingying Song; Zhengguo Cui (Marine Pollution Bulletin, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Suppression of the vortex-induced vibration of the cylinder by the baffle plates at different submerged depths - Yongjian Zhong; Huichao Li; Baoshou Zhang; Fujun Diao; Boyang Li; Ying Cui (Ocean Engineering, 2024)

Phytochrome B interacts with LIGULELESS1 to control plant architecture and density tolerance in maize - Qingbiao Shi; Ying Xia; Qibin Wang; Kaiwen Lv; Hengjia Yang; Lianzhe Cui; Yue Sun; Xiaofei Wang; Qing Tao; Xiehai Song; Di Xu; Wenchang Xu; et al. (Molecular Plant, 2024)

Early detection of nicosulfuron toxicity and physiological prediction in maize using multi-branch deep learning models and hyperspectral imaging - Tianpu Xiao; Li Yang; Dongxing Zhang; Tao Cui; Xiaoshuang Zhang; Ying Deng; Hongsheng Li; Haoyu Wang (Journal of Hazardous Materials, 2024)

Changes in pCO2 and climate paced by grand orbital cycles in the late Cenozoic - Yifei Zhang; Qiang Fang; Huaichun Wu; Christian Zeeden; Ying Cui; Meinan Shi; Shihong Zhang; Tianshui Yang; Haiyan Li (Global and Planetary Change, 2024)

pH-dependent growth of alumina nanorods with a high aspect ratio for enhanced propane dehydrogenation performance - Haowei Wang; Wen-Cui Li; Ying Ma; Yu Zhang; Shu-Zhen Zhou; An-Hui Lu (Chemical Engineering Journal, 2024)

LncRNA CCRR maintains Ca2+ homeostasis against myocardial infarction through the FTO-SERCA2a pathway - Hua Yang; Lina Xuan; Shengjie Wang; Huishan Luo; Xiaomeng Duan; Jianjun Guo; Shijia Cui; Jieru Xin; Junwei Hao; Xiufang Li; Jun Chen; Feihan Sun; et al. (Science China Life Sciences, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Characterization of adaptive expression regulation of yellowtail kingfish (Seriola lalandi) leptin, receptor, and receptor overlapping transcript genes in response to fasting and re-feeding strategies - Xin Cai; Ying Li; Aijun Cui; Yan Jiang; Bin Wang; Zhaojun Meng; Yongjiang Xu (Fish Physiology and Biochemistry, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

High dissolved oxygen regulation by side-stream supersaturated oxygenation impedes black-odor removal from rivers affected by combined sewer overflows - Qiuheng Zhu; Zhiyuan Wang; Ying Xiong; Guowen Li; Jianglong Cui; Xiaolong Zhu; Lieyu Zhang; Qiuwen Chen (Journal of Cleaner Production, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

H*ads dynamics engineering via bimetallic Pd–Cu@MXene catalyst for enhanced electrocatalytic hydrodechlorination - Lan-Ying Liu; Min-Hua Cui; John Justo Ambuchi; Shi-Ming Niu; Xin-Hui Li; Wo-Long Wang; He Liu; Guo-Shuai Liu; Ai-Jie Wang (Environmental Research, 2024)

Engineering multifunctional phase change composites enabled by dual-interpenetrating hybrid scaffold for excellent thermal conductivity and electromagnetic absorption - Boyang Hu; Hong Guo; Ying Cui; Jiaye Li; Min Cao; Weiyan Qi; Xiwei Cao; Baoan Li (Chemical Engineering Journal, 2024)

Correction to: Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2024)

Enhancing the health benefits of air quality improvement: a comparative study across diverse scenarios - Chuang Han; Chuanlong Cheng; Ying Liu; Qidi Fang; Chunyu Li; Feng Cui; Xiujun Li (Environmental Science and Pollution Research, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

The EDLL motif-containing transcription factor MaERF96L positively regulates starch degradation during banana fruit ripening - Wan-shan Xie; Yun-yi Xiao; Zong-li Liu; Xiao-nan Li; Mei-zhi Cui; Jian-wen Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ying-ying Yang (Postharvest Biology and Technology, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Divergent growth and responses of conifer and broad-leaved trees to warming-drying climate in a semi-arid region, northern China - Ying Zhao; Junxia Li; Yuting Jin; Tsun Fung Au; Di Cui; Zhenju Chen (European Journal of Forest Research, 2024)

A Novel Bacillus amyloliquefaciens Specifically Improving the Solubility and Antioxidant Activities of Edible Bird’s Nest - Xin-Lin Li; Jian-Mei Lian; Xiao-Ling Chen; Qun-Yan Fan; Ying Yan; Feng-Jie Cui (Current Microbiology, 2024)

Research on channel selection of low-carbon product considering advertising promotion under substitute competition - Haiyan Li; Qihan Cui; Lei Dou; Han Song; Ying Dai; Xinran Hu (Environment, Development and Sustainability, 2024)

Patient-derived pathogenic microbe deposition enhances exposure risk in pediatric clinics - Wan Wang; Zongyao Qiu; Hui Li; Xiaorong Wu; Ying Cui; Lixiang Xie; Bozhen Chang; Peipei Li; Hong Zeng; Tao Ding (Science of The Total Environment, 2024)

Waste cigarette butts-templated synthesis of in-situ graphitic carbon-doped ZnO fibers boosting dual-selectivity NO2/butanone at different temperatures - Zhao-Qi Cui; Ze Wei; Cong Chen; Yuan-Yuan Sun; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Rice N-biofertilization by inoculation with an engineered photosynthetic diazotroph - Yan Zeng; Mengmei Wang; Yunkai Yu; Lida Wang; Lingwei Cui; Chang Li; Ying Liu; Yanning Zheng (World Journal of Microbiology and Biotechnology, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Study on the Adsorption Performance of a Vortex Suction Cup under Varying Diameters of Underwater Structure Tubes - Qinyun Tang; Ying Du; Zhaojin Liu; Shuo Zhang; Qiang Zhao; Yingxuan Li; Liquan Wang; Tong Cui; Gang Wang (Journal of Marine Science and Engineering, 2024)
In certain precision work scenarios, underwater robots require the ability to adhere to surfaces in order to perform tasks effectively. An efficient and stable suction device plays a pivotal role in the functionality of such underwater robots. The vortex suction cup, distinguished by its uncomplicated design, high suction efficiency, and capability for non-contact adhesion, holds significant promise for integration into underwater robotic systems. This paper presents a novel design for a vortex suction cup and investigates its suction force and torque when encountering surfaces with varying curvature radii using Computational Fluid Dynamics (CFD) simulations and experimental testing. These findings offer valuable insights for the development of robots capable of adapting to underwater structures of different dimensions. Results from both experiments and simulations indicate that reducing the curvature radius of the adhered surface results in a decrease in suction force and an increase in torque exerted on the suction cup. As the adhered surface transitions from flat to a curvature radius of 150 mm, the adhesion force of our proposed vortex suction cup decreases by approximately 10%, while the torque increases by approximately 20% to 30%. Consequently, the adhesion efficiency of the suction cup decreases by about 25% to 30%.

The structural change and determinants of global carbon footprint network embodied in international migration: A social network analysis - Ying Li; Chen Jiang; Xiaofan Li; Jinzhu Zhang; Yutao Wang; Xuechun Yang; Qi Cui; Yu Liu (Journal of Cleaner Production, 2024)

Revealing the activity and selectivity of atomically dispersed Ni in Zn3In2S6 for benzyl alcohol photoreforming - Denny Gunawan; Li Yuan Lau; Jodie A. Yuwono; Priyank V. Kumar; Louis Oppong-Antwi; Inga Kuschnerus; Shery L.Y. Chang; Rosalie K. Hocking; Rose Amal; Jason Scott; Cui Ying Toe (Chemical Engineering Journal, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Establishment of tissue culture regeneration system of Ficus tikoua - Xufei Li; Qianxia Li; Ying Cui; Tongfei Liu; Yanni Zhang (In Vitro Cellular & Developmental Biology - Plant, 2024)

Effects of extreme temperature events on deaths and its interaction with air pollution - Chuanlong Cheng; Ying Liu; Chuang Han; Qidi Fang; Feng Cui; Xiujun Li (Science of The Total Environment, 2024)

The role of fungi in the formation and instability of halophilic aerobic granular sludge in a continuous flow reactor - Hui-Kai Liang; You-Wei Cui; Jin-Lei Yan; Hui-Juan Yan; Zhen-Ying Li; Yu-Bo Cui (Journal of Water Process Engineering, 2024)

Recent advances and trends of carbon-based biocarriers for performance enhancement of anaerobic membrane bioreactor system - Ying Liu; Xuyan Cui; Xinbo Zhang; Junzhi Ren; Hongxia Li; Zhiwen Wang; Wenshan Guo; Huu Hao Ngo (Journal of Water Process Engineering, 2024)

Differential response of Hg-methylating and MeHg-demethylating microbiomes to dissolved organic matter components in eutrophic lake water - Zhengyu Wu; Zhike Li; Bo Shao; Ji Chen; Xiaomei Cui; Xiaoyu Cui; Xianhua Liu; Ying Xin Zhao; Qiang Pu; Jiang Liu; Wei He; Yiwen Liu; et al. (Journal of Hazardous Materials, 2024)

Enhanced hydroisomerization of n-heptane over bifunctional catalysts with highly dispersed Pd nanoparticles supported on H-Yβ composite zeolite - Yu-Hong Kang; Xiao-Qi Zhang; Juan Gao; Guang-Hui Liu; Yan-Jun Li; Yong Gao; Jin-Jun Bai; Ai-Min Wang; Xian-Yong Wei; Cui-Ying Lu (Chemical Engineering Journal, 2024)

Acetylcholine Analog-Modified Albumin Nanoparticles for the Enhanced and Synchronous Brain Delivery of Saponin Components of Panax Notoginseng - Ying Yu; Li Yun Wang; Yan Chi Liu; Hao Cui; Cheng Yuan; Cheng Xiao Wang (Pharmaceutical Research, 2024)

Establishment of an immortalized cell line derived from human adenomyosis ectopic lesions - Zilu Wang; Fengxin Cui; Yinuo Chen; Hongyun Liu; Yiran Zhang; Yaxin Shi; Yinuo Zhang; Yanfei Wang; Na Liang; Li Xu; Ying Liu; Zhiyong Liu; et al. (Tissue and Cell, 2024)

Clonally derived chicken primordial germ cell lines maintain biological characteristics and proliferative potential in long-term culture - Ying-Jie Niu; Wenjie Ren; Guangzheng Liu; Kai Jin; Dan Zheng; Qisheng Zuo; Yani Zhang; Xiang-Shun Cui; Guohong Chen; Bichun Li (Theriogenology, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

7-Methoxy-13-dehydroxypaxilline: New indole diterpenoid from an endophytic fungus Penicillium sp. Nb 19 - Jing Yu; Jia-Peng Wang; Shi-Fang Liu; Cui-Yun Yin; De-Ying Tang; Yi-Hang Li; Li-Xia Zhang (Natural Product Research, 2024)

Low glycemic index noodle and pasta: Cereal type, ingredient, and processing - Congli Cui; Yong Wang; Jian Ying; Weibiao Zhou; Dong Li; Li-jun Wang (Food Chemistry, 2024)

3D Printing windows and rheological properties for normal maize starch/sodium alginate composite gels - Ying Cui; Fan Yang; Chang-sheng Wang; Andreas Blennow; Changyong Li; Xingxun Liu (Food Hydrocolloids, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

High capillary effect and solar dual-drive nanofibrillated cellulose aerogels for efficient crude oil spill cleanup - Bingjie Fan; Xueming Bao; Shanshan Pan; Ying Liu; Yuanyuan Yu; Li Cui; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Synergistic effect between Ni single atoms and Ni nanoparticles for effectively boosting sustainable co-electrolysis of CO2 and hydrazine - Min Li; Ye Hu; Wenhui Fang; Shixian Xin; Ying Wu; Yutao Cao; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Baicalin exerts neuroprotective actions by regulating the Nrf2-NLRP3 axis in toxin-induced models of Parkinson's disease - Jiahua Huang; Xinyue Zhang; Xueping Yang; Qingyun Yv; Fanlong Ye; Sheng Chen; Ying Cui; Linting Gu; Min Zhu; Wenwei Li (Chemico-Biological Interactions, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Changes in years of life lost and life expectancy by reducing air pollution - Ying Liu; Shuxia Yang; Chunyu Li; Qidi Fang; Chuang Han; Chuanlong Cheng; Yunxian Cao; Feng Cui; Xiujun Li (Air Quality, Atmosphere & Health, 2024)

Antibacterial properties and mechanism of nanometer zinc oxide composites - Ying Wang; Jiawei Liu; Ting Wang; Li-Zhi Liu; Chengcheng Tian; Ye Cui; Wenjun Shao; Xia Hua; Ying Shi; Yuanxia Wang (Food Packaging and Shelf Life, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

microRNA-944 inhibits breast cancer cell proliferation and promotes cell apoptosis by reducing SPP1 through inactivating the PI3K/Akt pathway - Ying Zhang; Shan Li; Xiangguo Cui; Yiliang Wang (Apoptosis, 2023)

Identifying the key factors affecting the trimethylamine N-oxide content of teleost fishes collected from the marginal seas of China and the epipelagic zone of the northwest Pacific Ocean - Qingjing Hu; Wanyu Zhao; Keming Qu; Ning An; Lingxiao Li; Yuqiu Wei; Ying Bai; Tao Jiang; Jufa Chen; Fangqun Dai; Hongsheng Wang; Zhengguo Cui (Science of The Total Environment, 2023)

Federated learning with SARIMA-based clustering for carbon emission prediction - Tianxu Cui; Ying Shi; Bo Lv; Rijia Ding; Xianqiang Li (Journal of Cleaner Production, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Elemental sulfur-driven autotrophic denitrification process for effective removal of nitrate in mariculture wastewater: Performance, kinetics and microbial community - Lu Wang; Jun Liu; Yongfu Li; Zhihao Liu; Long Zhang; Hong Che; Hongwu Cui; Ying Zhang (Chemosphere, 2023)

NAT10 regulates the repair of UVB-induced DNA damage and tumorigenicity - Zizhao Yang; Emma Wilkinson; Yan-Hong Cui; Haixia Li; Yu-Ying He (Toxicology and Applied Pharmacology, 2023)

Effects of dietary resveratrol supplementation in cattle on the anti-oxidative capacity and meat quality of beef steaks under high‑oxygen packaging - Ying Cui; Jiajing Qi; Jiqiang Li; Yimin Zhang; Xiaoyin Yang; Luo Xin; Lebao Niu; Baochen Xu; Zhanyu Qian; Lixian Zhu; Rongrong Liang (Meat Science, 2023)

Phthalates (PAEs) and reproductive toxicity: Hypothalamic-pituitary-gonadal (HPG) axis aspects - Ying Zhang; Yang Yang; Yue Tao; Xiangyong Guo; Yunhe Cui; Zixu Li (Journal of Hazardous Materials, 2023)

Eustatic change across the Paleocene-Eocene Thermal Maximum in the epicontinental Tarim seaway - Jingxin Jiang; Xiumian Hu; Juan Li; Eduardo Garzanti; Shijun Jiang; Ying Cui; Yasu Wang (Global and Planetary Change, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

Tandem fractionation technologies (TAFT) benefit multi-functional porous carbon toward lignin valorization - Kai Chen; Tao Xu; Shi-Chang Liu; Li Wang; Jia-Qi Cui; Zhi-Hua Liu; Bing-Zhi Li; Ying-Jin Yuan (Chemical Engineering Journal, 2023)

One-pot preparation of bi-functional POSS-based hybrid monolith via photo-initiated polymerization for isolation of extracellular vesicles - Qi Zhang; Mengxi Chen; Fang Xu; Wen Wu; Xintong Luo; Ying Wang; Jiaxi Li; Xuanhao Cui; Yujia Tan; Zhi Li; Yujie Lin; Haiyang Zhang; et al. (Analytica Chimica Acta, 2023)

Agrochemical-mediated cardiotoxicity in zebrafish embryos/larvae: What we do and where we go - Yang Yang; Yue Tao; Zixu Li; Yunhe Cui; Jinzhu Zhang; Ying Zhang (Critical Reviews in Environmental Science and Technology, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Nanomedicine targets endogenous copper ions for disease diagnosis and therapy - Xiao Li; Ying Cui; Tianhua Zhou; Jianguang Li; Pei Lu; Lihui Yuwen; Lianhui Wang; Lixing Weng (Chemical Engineering Journal, 2023)

The ionome and proteome landscape of aging in laying hens and relation to egg white quality - Guang Li; Yuqing Feng; Jian Cui; Qihang Hou; Tanfang Li; Meiting Jia; Zhengtian Lv; Qiuyu Jiang; Ying Wang; Ming Zhang; Lin Wang; Zengpeng Lv; et al. (Science China Life Sciences, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Surfactant-assisted ethylenediamine for the deconstruction and conversion of corn stover biomass - Jia-Qi Cui; Ya-Qi Li; Samuel Ntakirutimana; Zhi-Hua Liu; Bing-Zhi Li; Ying-Jin Yuan (Bioresource Technology, 2023)

Interferons as negative regulators of ILC2s in allergic lung inflammation and respiratory viral infections - Cui Wang; Zhaoxiang Du; Ranhui Li; Ying Luo; Cuiming Zhu; Nan Ding; Aihua Lei (Journal of Molecular Medicine, 2023)

Knockdown of USF2 inhibits pyroptosis of podocytes and attenuates kidney injury in lupus nephritis - Ying Xie; Xiaoying Li; Wenli Deng; Nan Nan; Huimei Zou; Lei Gong; Min Chen; Jie Yu; Peilei Chen; Daolin Cui; Fan Zhang (Journal of Molecular Histology, 2023)

In-situ detection equipment for radon-in-water: unattended operation and monthly investigations - Chunqian Li; Meng Li; Guangquan Chen; Huaming Yu; Chenglun Zhang; Wen Liu; Jinjia Guo; Shibin Zhao; Lijun Song; Xiliang Cui; Ying Chai; Lu Cao; et al. (Acta Oceanologica Sinica, 2023)

Denitrification performance and in-situ fermentation mechanism of the wastepaper-flora slow-release carbon source - Ying Cui; Bowei Zhao; Xiao Zhang; Xiao Ma; Aijuan Zhou; Sufang wang; Xiuping Yue; Jianzheng Li; Jia Meng (Bioresource Technology, 2023)

Integrating polygenic and clinical risks to improve stroke risk stratification in prospective Chinese cohorts - Qingmei Cui; Fangchao Liu; Jianxin Li; Xiaoge Niu; Zhongying Liu; Chong Shen; Dongsheng Hu; Keyong Huang; Shufeng Chen; Jie Cao; Xiaoqing Liu; Ling Yu; et al. (Science China Life Sciences, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Study on the feasibility of carbon source recovery by upflow anaerobic sludge blanket in simulated municipal wastewater - Xiao Zhang; Bowei Zhao; Rui Li; Ying Cui; Fei Xie; Aijuan Zhou; Jinping Li; Xiuping Yue (Science of The Total Environment, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Conservation and divergence of flg22, pep1 and nlp20 in activation of immune response and inhibition of root development - Yan Huang; Junmei Cui; Meng Li; Rongqian Yang; Yang Hu; Xiaosong Yu; Ying Chen; Qiqi Wu; Huipeng Yao; Guozhi Yu; Jinya Guo; Huaiyu Zhang; et al. (Plant Science, 2023)

The BrAFP1 promoter drives gene-specific expression in leaves and stems of winter rapeseed (Brassica rapa L.) under cold induction - Xiaoyun Dong; Zigang Liu; Jiaping Wei; Guoqiang Zheng; Hui Li; Ying Wang; Haiyan Tian; Junmei Cui; Zefeng Wu; Xiaodong Cao; Chunmei Xu (Plant Science, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Probability of rainstorm and flood disasters due to extreme precipitation in Fen River Basin, China - Ying Li; Jin Sun; Xiaoqi Cui; Chenchen Jia; Jinlong Chao (Environmental Science and Pollution Research, 2023)

A new chamigrane sesquiterpene from the rice fermentation of Antrodiella albocinnamomea - Min Guo; Ying-Zhong Liang; Xiu-Ming Cui; Lin-Jiao Shao; Yin-Fei Li; Xiao-Yan Yang (Natural Product Research, 2023)

Hazardous substances and their removal in recirculating aquaculture systems: A review - Hao Li; Zhengguo Cui; Hongwu Cui; Ying Bai; Zhendong Yin; Keming Qu (Aquaculture, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Ying-Wen Mu; Dong Cheng; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2023)

Distribution characteristics and environmental effects of non-methane hydrocarbons in the East China Sea - Wen-Zhu Qiao; Ying-Cui Wu; Ping Wang; Jian Wang; Li-Min Zhou; Si-Tong Li; Hong-Hai Zhang (Continental Shelf Research, 2023)

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

Molecular mechanism of adsorbing triclocarban by the activated sludge in wastewater treatment systems - Hao Wang; Hanlin Cui; Xiaodan Ma; Carolyn R. Cornell; Liying Zhang; Yijun Ren; Minghan Li; Ying Liu; Shu-Hong Gao; Zhiling Li; Ai-Jie Wang; Jizhong Zhou; et al. (Chemical Engineering Journal, 2023)

The effect of episodic foresight on intertemporal decision-making: the role of future self-continuity and perceived control - Hong-Yue Sun; Yuan-Ping Jiang; Xin Wang; Li-Ying Cui; Hong-Mei Sun (Cognitive Processing, 2023)

Real-ambient particulate matter exposure-induced FGFR1 methylation contributes to cardiac dysfunction via lipid metabolism disruption - Benying Li; Yanan Liang; Hongxu Bao; Daochuan Li; Ying Zhang; Xinyu Dun; Zijian Xu; Andong Ji; Zhen Zhang; Yahui Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Insights on nitrogen and phosphorus removal mechanism in a single-stage Membrane Aeration Biofilm Reactor (MABR) dominated by denitrifying phosphorus removal coupled with anaerobic/aerobic denitrification - Ming Li; Xiwei Cao; Ziqing Wu; Jiaye Li; Ying Cui; Jun Liu; Baoan Li (Journal of Water Process Engineering, 2023)

The eisosomes contribute to acid tolerance of yeast by maintaining cell membrane integrity - Chao Li; Jun Lu; Xue-Jiao Yan; Chang-Wen Li; Liang-Cai Lin; Dong-Guang Xiao; Cui-Ying Zhang (Food Microbiology, 2023)

Metagenomic study of carbon metabolism in black soil microbial communities under lead-lanthanum stress - Yue Tao; Lu Shen; Siyue Han; Zixu Li; Yunhe Cui; Yulong Lin; Jianhua Qu; Ying Zhang (Journal of Hazardous Materials, 2023)

Novel flavan-3-ol-dithiothreitol conjugates derived from the degradation of grape seed proanthocyanidins and their neuroprotective potential - Meng Huang; Meng Li; Ying Zhang; Huan Gong; Yuju Zhou; Danping Zhu; Lingxi Li; Ning Ma; Yan Cui (Food Chemistry, 2023)

Soil microbial trait-based strategies drive the storage and stability of the soil carbon pool in Robinia pseudoacacia plantations - Min Zhang; Xiaoxiong Bai; Ying Wang; Yan Li; Yongxing Cui; Sile Hu; M. Adams Jonathan; Liguo Dong; Xuan Yu (CATENA, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Barley β-glucan inhibits digestion of soybean oil in vitro and lipid-lowering effects of digested products in cell co-culture model - Jiaying Li; Yurong Zhou; Jiayan Zhang; Ling Cui; Haina Lu; Ying Zhu; Yansheng Zhao; Songtao Fan; Xiang Xiao (Food Research International, 2023)

Parthenolide inhibits proliferation of cells infected with Kaposi’s sarcoma-associated herpesvirus by suppression of the NF-κB signaling pathway - Ying Li; Huiling Xu; Xiaohua Tan; Qinghua Cui; Wenyi Gu; Zemin Pan; Lei Yang; Shuyuan Wu; Xiaolu Wang; Dongmei Li (Archives of Virology, 2023)

Numerical Investigation on the Hydrodynamic Response of Pentamaran—Resistance Analysis of Different Outrigger Inclination Angles - Pengwei Hu; Ying Cui; Chenyu Zhao; Yanan Li; Boyang Li (Journal of Marine Science and Engineering, 2023)
Due to the interference between the main hull and the outrigger of the pentamaran, resistance is greatly affected. Therefore, research on the pentamaran front outrigger inclination angle has further practical significance for reducing resistance. In this study, the pentamaran front outrigger inclination angle was analyzed by CFD method, the ship motion in waves was simulated by overlapping grid technology, and the resistance of the pentamaran in static water and waves was predicted by using the unsteady RANS equation. First, a series of validation studies were carried out for the numerical methods used in the study. Then, the influence of the front outrigger inclination angle on the pentamaran resistance performance under different working conditions is calculated and discussed. In order to analyze the influence of the change of the front outrigger inclination angle on the resistance, free surface wave-making and hull pressure are further discussed. The results show that the influence of the front outrigger inclination angle change on the resistance of the pentamaran has a certain rule, and the resistance of the pentamaran can be reduced by adjusting the front outrigger inclination angle.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

A review and evaluation of nonroad diesel mobile machinery emission control in China - Pengju Bie; Liang Ji; Huanxing Cui; Gang Li; Shunli Liu; Ying Yuan; Kebin He; Huan Liu (Journal of Environmental Sciences, 2023)

Pilot test of low-rank coal pyrolysis coupled with gasification to hydrogen-rich gas for direct reduced iron: Process modeling, simulation and thermodynamic analysis - Qian Liu; Ying-jie Zhao; Yi Huang; Feng Pei; Yang Cui; Li-juan Shi; Li-ping Chang; Qun Yi (Fuel, 2023)

Preparation, structural characterization and neuroprotective effects to against H2O2-induced oxidative damage in PC12 cells of polysaccharides from Pleurotus ostreatus - Liuya Wang; Kun Li; Yidan Cui; Haihai Peng; Ying Hu; Zhenyuan Zhu (Food Research International, 2023)

Impacts of mowing and N addition on soil organic phosphorus mineralization rates in a semi-natural grassland in Northeast China - Haiying Cui; Mingcai Fan; Yunbo Wang; Xiaochong Zhang; Wanling Xu; Yanan Li; Wenzheng Song; Jian-Ying Ma; Wei Sun (Plant and Soil, 2023)

Therapeutic Effects of Human Pluripotent Stem Cell-Derived Mesenchymal Stem Cells on a Murine Model of Acute Type-2-Dominated Airway Inflammation - Si-Yuan Ma; Ning Zhao; Lele Cui; Ying Li; Hang Zhang; Jing Wang; Jie Pang; Ming Wang; Chengshuo Wang; Sun Ying; Zi-Bing Jin; Luo Zhang (Stem Cell Reviews and Reports, 2022)

Reading-related Brain Function Restored to Normal After Articulation Training in Patients with Cleft Lip and Palate: An fMRI Study - Liwei Sun; Wenjing Zhang; Mengyue Wang; Songjian Wang; Zhen Li; Cui Zhao; Meng Lin; Qian Si; Xia Li; Ying Liang; Jing Wei; Xu Zhang; et al. (Neuroscience Bulletin, 2022)

Metabolic changes of the reduction of manganese intake in the hepatic encephalopathy rat: NMR- and MS-based metabolomics study - Jingjing Lu; Ying Li; Cui Zhang; Xiuying Yang; Jinwei Qiang (BioMetals, 2022)

Polygenic control of the wavy coat of the NCT mouse: involvement of an intracisternal A particle insertional mutation of the protease, serine 53 (Prss53) gene, and a modifier gene - Masayuki Mori; Chang Liu; Takahiro Yoshizawa; Hiroki Miyahara; Jian Dai; Yuichi Igarashi; Xiaoran Cui; Ying Li; Xiaojing Kang; Keiichi Higuchi (Mammalian Genome, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Trachyte reservoir characteristics and favorable reservoir identification and prediction in the J34 block, Eastern Sag - Chenglong Ma; Ying Wu; Tuan Gu; Bin Zhang; Yu Gang Li; Ying Jie Zhang; Wen Bo Dong; Jie Cui (Acta Geophysica, 2022)

Correction to: GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinfammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Manure fertilization enhanced microbial immigration in the wheat rhizosphere - Ye Liu; Shuikuan Bei; Oladele Olatunde; Ying Li; Xingjie Wu; Hongyan Zhang; Zhenling Cui; Christopher Rensing; Jingjing Peng (Journal of Soils and Sediments, 2022)

Effect of electronic cigarette and tobacco smoking on the human saliva microbial community - Xue Wang; Qili Mi; Ji Yang; Ying Guan; Wanli Zeng; Haiying Xiang; Xin Liu; Wenwu Yang; Guangyu Yang; Xuemei Li; Yinshan Cui; Qian Gao (Brazilian Journal of Microbiology, 2022)

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Stable Isotopes Reveal Water Vapor Sources of Precipitation over the Jiaolai Plain, Shandong Peninsula, China - Ying Wang; Bu-li Cui; Dong-sheng Li; Ya-xuan Wang; Wan-xin Yu; He-hua Zong (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Migration and Deposition Characteristics of Particles in Sand Layers with Fluctuating Water Levels - Xianze Cui; Tao Wen; Jin Li; Dazhou Wu; Yong Fan; Ying Jin; Siyuan He; Yucong Pan (Water, Air, & Soil Pollution, 2022)

miR-1290 promotes IL-8-mediated vascular endothelial cell adhesion by targeting GSK-3β - Hongxin Xu; Ying Cui; Xianwei Liu; Xiao Zheng; Jiaqing Liu; Xinxin Hu; Fuhua Gao; Xiaoyan Hu; Mei Li; Xiaoqing Wei; Ying Gao; Ying Zhao (Molecular Biology Reports, 2022)

HTRPCA: Hypergraph Regularized Tensor Robust Principal Component Analysis for Sample Clustering in Tumor Omics Data - Yu-Ying Zhao; Cui-Na Jiao; Mao-Li Wang; Jin-Xing Liu; Juan Wang; Chun-Hou Zheng (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Induced production of a new polyketide in Penicillium sp. HS-11 by chemical epigenetic manipulation - You-Min Ying; Ling Li; Hang-Fei Yu; Yi-Lian Xu; Lu Huang; Wei Mao; Cui-Ping Tong; Zhi-Dong Zhang; Zha-Jun Zhan; Yun Zhang (Natural Product Research, 2021)

A cross-sectional study of chemotherapy-related AKI - Xin Kang; Xizi Zheng; Damin Xu; Tao Su; Ying Zhou; Jing Ji; Qi Yu; Yimin Cui; Li Yang (European Journal of Clinical Pharmacology, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinflammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2021)

Local climate adaptation and gene flow in the native range of two co‐occurring fruit moths with contrasting invasiveness - Li‐Jun Cao; Bing‐Yan Li; Jin‐Cui Chen; Jia‐Ying Zhu; Ary A. Hoffmann; Shu‐Jun Wei (Molecular Ecology, 2021)
Invasive species pose increasing threats to global biodiversity and ecosystems. While previous studies have characterized successful invaders based on ecological traits, characteristics related to evolutionary processes have rarely been investigated. Here we compared gene flow and local adaptation using demographic analyses and outlier tests in two co‐occurring moth pests across their common native range of China, one of which (the peach fruit moth, Carposina sasakii ) has maintained its native distribution, while the other (the oriental fruit moth, Grapholita molesta ) has expanded its range globally during the past century. We found that both species showed a pattern of genetic differentiation and an evolutionary history consistent with a common southwestern origin and northward expansion in their native range. However, for the noninvasive species, genetic differentiation was closely aligned with the environment, and there was a relatively low level of gene flow, whereas in the invasive species, genetic differentiation was associated with geography. Genome scans indicated stronger patterns of climate‐associated loci in the noninvasive species. While strong local adaptation and reduced gene flow across its native range may have decreased the invasiveness of C . sasakii , this requires further validation with additional comparisons of invasive and noninvasive species across their native range.

Gut Microbial Metabolites in Parkinson’s Disease: Implications of Mitochondrial Dysfunction in the Pathogenesis and Treatment - Yixuan Liang; Li Cui; Jiguo Gao; Mingqin Zhu; Ying Zhang; Hong-Liang Zhang (Molecular Neurobiology, 2021)
The search for therapeutic targets for Parkinson’s disease (PD) is hindered by the incomplete understanding of the pathophysiology of the disease. Mitochondrial dysfunction is an area with high potential. The neurobiological signaling connections between the gut microbiome and the central nervous system are incompletely understood. Multiple lines of evidence suggest that the gut microbiota participates in the pathogenesis of PD. Gut microbial dysbiosis may contribute to the loss of dopaminergic neurons through mitochondrial dysfunction. The intervention of gut microbial metabolites via the microbiota-gut-brain axis may serve as a promising therapeutic strategy for PD. In this narrative review, we summarize the potential roles of gut microbial dysbiosis in PD, with emphasis on microbial metabolites and mitochondrial function. We then review the possible ways in which microbial metabolites affect the central nervous system, as well as the impact of microbial metabolites on mitochondrial dysfunction. We finally discuss the possibility of gut microbiota as a therapeutic target for PD.

MR T1 mapping for quantifying brain manganese deposition in type C hepatic encephalopathy rats - Cui Zhang; Ying Li; Jingjing Lu; Xiuying Yang; Jie Wang; Jinwei Qiang (BioMetals, 2021)

Physical Modelling of Offshore Wind Turbine Foundations for TRL (Technology Readiness Level) Studies - Subhamoy Bhattacharya; Domenico Lombardi; Sadra Amani; Muhammad Aleem; Ganga Prakhya; Sondipon Adhikari; Abdullahi Aliyu; Nicholas Alexander; Ying Wang; Liang Cui; Saleh Jalbi; Vikram Pakrashi; et al. (Journal of Marine Science and Engineering, 2021)
Offshore wind turbines are a complex, dynamically sensitive structure due to their irregular mass and stiffness distribution, and complexity of the loading conditions they need to withstand. There are other challenges in particular locations such as typhoons, hurricanes, earthquakes, sea-bed currents, and tsunami. Because offshore wind turbines have stringent Serviceability Limit State (SLS) requirements and need to be installed in variable and often complex ground conditions, their foundation design is challenging. Foundation design must be robust due to the enormous cost of retrofitting in a challenging environment should any problem occur during the design lifetime. Traditionally, engineers use conventional types of foundation systems, such as shallow gravity-based foundations (GBF), suction caissons, or slender piles or monopiles, based on prior experience with designing such foundations for the oil and gas industry. For offshore wind turbines, however, new types of foundations are being considered for which neither prior experience nor guidelines exist. One of the major challenges is to develop a method to de-risk the life cycle of offshore wind turbines in diverse metocean and geological conditions. The paper, therefore, has the following aims: (a) provide an overview of the complexities and the common SLS performance requirements for offshore wind turbine; (b) discuss the use of physical modelling for verification and validation of innovative design concepts, taking into account all possible angles to de-risk the project; and (c) provide examples of applications in scaled model tests.

High-resolution estimation of ambient sulfate concentration over Taiwan Island using a novel ensemble machine-learning model - Lulu Cui; Qingwei Ma; Rui Li; Hongbo Fu; Ziyu Zhang; Liwu Zhang; Ying Chen (Environmental Science and Pollution Research, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

In vitro antifungal susceptibility of Sporothrix globosa isolates from Jilin Province, northeastern China: comparison of yeast and mycelial phases - Yang Song; Shanshan Li; Ying Shi; Lipei Zhao; Yu Cui; Lei Yao; Yu Zhen; Ruili Chen; Yan Cui (Brazilian Journal of Microbiology, 2021)

MicroRNA-520c-3p suppresses vascular endothelium dysfunction by targeting RELA and regulating the AKT and NF-κB signaling pathways - Yan Jiao; Dandan Zhao; Fuhua Gao; Xiaoyan Hu; Xinxin Hu; Mei Li; Ying Cui; Xiaoqing Wei; Ce Xie; Ying Zhao; Ying Gao (Journal of Physiology and Biochemistry, 2021)

Detection and genetic characteristics of porcine bocavirus in central China - Lan-Lan Zheng; Jian-Tao Cui; Han Qiao; Xin-Sheng Li; Xiao-Kang Li; Hong-Ying Chen (Archives of Virology, 2021)

Connexin 36 Mediates Orofacial Pain Hypersensitivity Through GluK2 and TRPA1 - Qian Li; Tian-Le Ma; You-Qi Qiu; Wen-Qiang Cui; Teng Chen; Wen-Wen Zhang; Jing Wang; Qi-Liang Mao-Ying; Wen-Li Mi; Yan-Qing Wang; Yu-Xia Chu (Neuroscience Bulletin, 2020)

The Effect of Iodine-Containing Vitamin Supplementation During Pregnancy on Thyroid Function in Late Pregnancy and Postpartum Depression in an Iodine-Sufficient Area - Zixiao Wang; Chenyang Li; Ying Teng; Yunping Guan; Li Zhang; Xi Jia; Dandan Cui; Jing Li; Haixia Guan (Biological Trace Element Research, 2020)

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

The nucleic acid positive rate and genotype distribution of human cytomegalovirus in human milk banks in China - Xiaoyu Min; Lin Wang; Aili Cui; Chunli Zhang; Dan Wang; Ying Liu; Zhenghong Li; Wenbo Xu (Archives of Virology, 2020)

GPR based RTM imaging technology for estimating rhizome diameters and application in the western China mining area - Fan Cui; Shuai Li; Jiong-Xuan Yuan; Jie-Bin Bai; Yu-Xuan Zhao; Ying-Ging Zhou (Applied Geophysics, 2020)

Identification of a novel COL4A5 mutation in the proband initially diagnosed as IgAN from a Chinese family with X-linked Alport syndrome - Zhihui Li; Peng Zhu; Hui Huang; Ying Pan; Peng Han; Huanhuan Cui; Zhijuan Kang; Mai Xun; Yi Zhang; Saijun Liu; Jian Wang; Jing Wu (Science China Life Sciences, 2019)

iTRAQ-based analysis of 17β-estradiol induced proteome in Chinese tongue sole Cynoglossus semilaevis - Ying Zhu; Yangzhen Li; Hailong Li; Lei Wang; Ning Zhang; Yang Liu; Liang Meng; Xiwen Xu; Zhongdian Dong; Min Wei; Hua Guo; Zhongkai Cui; et al. (Journal of Oceanology and Limnology, 2019)

The orphan nuclear receptor NUR77 promotes trophoblast invasion at early pregnancy through paracrine placental growth factor - Xiao-Cui Li; Xiang-Jie Yin; Wei Hong; Jie Liu; Feng Jin; Bei-Ying Wang; Yu-Mei Wang; Fu-Ju Tian (Journal of Molecular Medicine, 2019)

MicroRNAs Involved in the Regulation of LC-PUFA Biosynthesis in Teleosts: miR-33 Enhances LC-PUFA Biosynthesis in Siganus canaliculatus by Targeting insig1 which in Turn Upregulates srebp1 - Jun Jun Sun; Li Guo Zheng; Cui Ying Chen; Jin Ying Zhang; Cui Hong You; Qing Hao Zhang; Hong Yu Ma; Óscar Monroig; Douglas R. Tocher; Shu Qi Wang; Yuan You Li (Marine Biotechnology, 2019)

Down-regulation of miR-377 suppresses high glucose and hypoxia-induced angiogenesis and inflammation in human retinal endothelial cells by direct up-regulation of target gene SIRT1 - Chunmei Cui; Yuehua Li; Ying Liu (Human Cell, 2019)

Glacier extent changes and possible causes in the Hala Lake Basin of Qinghai-Tibet Plateau - Dong-Sheng Li; Bu-Li Cui; Ying Wang; Bei Xiao; Bao-Fu Jiang (Journal of Mountain Science, 2019)

Seabed deposition and erosion change and influence factors in the Yangshan Deepwater Port over the years - Shuhua Zuo; Hualiang Xie; Xiaoming Ying; Cheng Cui; Yuxin Huang; Huaiyuan Li; Mingxiao Xie (Acta Oceanologica Sinica, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Accelerated Versus Conventional Corneal Collagen Cross-Linking in the Treatment of Keratoconus: A Meta-analysis and Review of the Literature - Yang Jiang; Shan Yang; Ying Li; Ge Cui; Thomas Chengxuan Lu (Interdisciplinary Sciences: Computational Life Sciences, 2019)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Anti-Hypertensive Action of Fenofibrate via UCP2 Upregulation Mediated by PPAR Activation in Baroreflex Afferent Pathway - Jian Guan; Miao Zhao; Chao He; Xue Li; Ying Li; Jie Sun; Wei Wang; Ya-Li Cui; Qing Zhang; Bai-Yan Li; Guo-Fen Qiao (Neuroscience Bulletin, 2019)

Altered Expression of Zinc Transporter ZIP12 in Broilers of Ascites Syndrome Induced by Intravenous Cellulose Microparticle Injection - Hao Cui; Jianxin Liu; Guming Xu; Xujiao Ren; Zhenbiao Li; Ying Li; Zhangyong Ning (Biochemical Genetics, 2019)

Integrated analysis of transcription factors and targets co-expression profiles reveals reduced correlation between transcription factors and target genes in cancer - Jinsheng Liang; Ying Cui; Yuhuan Meng; Xingsong Li; Xueping Wang; Wanli Liu; Lizhen Huang; Hongli Du (Functional & Integrative Genomics, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

The complete mitochondrial genome of an endangered reef gastropods Trochus pyramis - Zhi-ying Zhao; Zhi-gang Tu; Jing Cui; Li-rong Bai (Conservation Genetics Resources, 2018)

A case study on the occurrence, transport, and fate of mercury species in a sewage treatment plant in Jiaozuo, China - Hao Liu; Ying Cui; Hua Li; Yuxiang Mao (Environmental Science and Pollution Research, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Ethanol extract of Rehmannia glutinosa exerts antidepressant-like effects on a rat chronic unpredictable mild stress model by involving monoamines and BDNF - Jun-Ming Wang; Li-Xin Pei; Yue-Yue Zhang; Yong-Xian Cheng; Chun-Ling Niu; Ying Cui; Wei-Sheng Feng; Gui-Fang Wang (Metabolic Brain Disease, 2018)

Proteomic analysis of human umbilical vein endothelial cells exposed to PM2.5 - Ji Zhu; Lin-wen-si Zhu; Jin-huan Yang; Ying-ling Xu; Cui Wang; Zhuo-yu Li; Wei Mao; De-zhao Lu (Journal of Zhejiang University-SCIENCE B, 2018)

Optimized staggered-grid finite-difference operators using window functions - Ying-Jun Ren; Jian-Ping Huang; Peng Yong; Meng-Li Liu; Chao Cui; Ming-Wei Yang (Applied Geophysics, 2018)

Responses of soil microbial community to nitrogen fertilizer and precipitation regimes in a semi-arid steppe - Yi-Fei Sun; Ju-Pei Shen; Cui-Jing Zhang; Li-Mei Zhang; Wen-Ming Bai; Ying Fang; Ji-Zheng He (Journal of Soils and Sediments, 2018)

Characterization of an endangered marine strombid gastropod Strombus luhuanus complete mitochondrial genome - Zhi-ying Zhao; Zhi-gang Tu; Li-rong Bai; Jing Cui (Conservation Genetics Resources, 2018)

The aflatoxin-detoxifizyme specific expression in the parotid gland of transgenic pigs - An-gang Lou; Jin-shun Cai; Xue-mei Zhang; Cheng-dou Cui; Ying-shu Piao; Li-zeng Guan (Transgenic Research, 2017)

Effects of endogenous hormones on variation of shoot branching in a variety of non-heading Chinese cabbage and related gene expression - Xue-Wei Cao; Hong-Mi Cui; Yuan Yao; Ai-Sheng Xiong; Xi-Lin Hou; Ying Li (Journal of Plant Biology, 2017)

Detection and Monitoring of Oil Spills Using Moderate/High-Resolution Remote Sensing Images - Ying Li; Can Cui; Zexi Liu; Bingxin Liu; Jin Xu; Xueyuan Zhu; Yongchao Hou (Archives of Environmental Contamination and Toxicology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities - Shuang-Xi Mei; Xu-Hong Li; Li-Guo Yang; Xiao-Hui Li; Jia-Ying Xie; Qi Yao; Mei Su; Tao Cui; Jing-Kun Wang; Zhao-Yun Zhu (Natural Product Research, 2017)

The accumulation and health risk of heavy metals in vegetables around a zinc smelter in northeastern China - Bo Li; Yanhong Wang; Yong Jiang; Guochen Li; Jiehua Cui; Ying Wang; Hong Zhang; Shicheng Wang; Sheng Xu; Ruzhen Wang (Environmental Science and Pollution Research, 2016)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

Geniposide alleviates depression-like behavior via enhancing BDNF expression in hippocampus of streptozotocin-evoked mice - Junming Wang; Peili Duan; Ying Cui; Qing Li; Yanran Shi (Metabolic Brain Disease, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

A Comparison of Different-Mode Fields Generated from Grounded-Wire Source Based on the 1D Model - Nan-Nan Zhou; Guo-qiang Xue; Hai Li; M. Younis; Dong-yang Hou; Hua-sen Zhong; Wei-ying Chen; Jiang-wei Cui (Pure and Applied Geophysics, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Morphology, sex steroid level and gene expression analysis in gonadal sex reversal of triploid female (XXX) rainbow trout (Oncorhynchus mykiss) - Gefeng Xu; Tianqing Huang; Xian Jin; Cunhe Cui; Depeng Li; Cong Sun; Ying Han; Zhenbo Mu (Fish Physiology and Biochemistry, 2016)

A novel Halomonas ventosae-specific virulent halovirus isolated from the Qiaohou salt mine in Yunnan, Southwest China - Chao-Qun Fu; Qin Zhao; Zhi-Ying Li; Yong-Xia Wang; Shi-Ying Zhang; Yong-Hong Lai; Wei Xiao; Xiao-Long Cui (Extremophiles, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2015)

Polycyclic aromatic hydrocarbons in the largest deepwater port of East China Sea: impact of port construction and operation - Juan-Ying Li; Yu Cui; Lei Su; Yiqin Chen; Ling Jin (Environmental Science and Pollution Research, 2015)

Exploration of copula function use in crop meteorological drought risk analysis: a case study of winter wheat in Beijing, China - Ying Li; Wei Gu; Weijia Cui; Zhiyun Chang; Yingjun Xu (Natural Hazards, 2015)

Isolation and characterization of thirty-eight microsatellite loci for the Pinus wangii, an endangered species - Zhi-Yong Zhang; Binbin Cui; Jian-Feng Mao; Xiao-Ming Pang; Ying-Yue Li (Conservation Genetics Resources, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Up-regulation of integrin α6β4 expression by mitogens involved in dairy cow mammary development - Feng Zhao; Chang Liu; Yu-Meng Hao; Bo Qu; Ying-Jun Cui; Na Zhang; Xue-Jun Gao; Qing-Zhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Novel polymorphic EST-derived microsatellite markers for the red-listed five needle pine, Pinus dabeshanensis - Zhi-Yong Zhang; Bin-Bin Cui; Jian-Feng Mao; Xiao-Ming Pang; Hui Liu; Ying-Yue Li (Conservation Genetics Resources, 2015)

Development of 36 novel polymorphic microsatellites for the critically endangered tree Pinus squamaia, by transcriptome database mining - Jian-Feng Mao; Bin-Bin Cui; Zhi-Yong Zhang; Hui Liu; Ying-Yue Li (Conservation Genetics Resources, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Upregulation of EHD2 after Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Ying Rui; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Maohong Cao (Journal of Molecular Neuroscience, 2014)

Functional analysis of FABP3 in the milk fat synthesis signaling pathway of dairy cow mammary epithelial cells - Meng-yao Liang; Xiao-ming Hou; Bo Qu; Na Zhang; Nan Li; Ying-jun Cui; Qing-zhang Li; Xue-jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2014)

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8 - Yu-bao Cui; Ying Zhou; Nan Wang; Fei-xiang Teng; Li-li Yu; Yong-hua Bian; Jin-xia Song; Li Yang; Cheng-bo Zhang (Immunologic Research, 2014)

A homolog of glyceraldehyde-3-phosphate dehydrogenase from Riemerella anatipestifer is an extracellular protein and exhibits biological activity - Ji-ye Gao; Cui-lian Ye; Li-li Zhu; Zhi-ying Tian; Zhi-bang Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Deep-Red Phosphorescent Iridium(III) Complexes Containing 1-(Benzo[b] Thiophen-2-yl) Isoquinoline Ligand: Synthesis, Photophysical and Electrochemical Properties and DFT Calculations - Gao-Nan Li; Ying Zou; Yi-Ding Yang; Jiao Liang; Feng Cui; Tao Zheng; Hui Xie; Zhi-Gang Niu (Journal of Fluorescence, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Dissipation and residue of metalaxyl and cymoxanil in pepper and soil - Xiangyun Liu; Yan Yang; Ying Cui; Huijun Zhu; Xiong Li; Zhining Li; Kankan Zhang; Deyu Hu (Environmental Monitoring and Assessment, 2014)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Halomonas qiaohouensis sp. nov., isolated from salt mine soil in southwest China - Yong-Xia Wang; Wei Xiao; Ming-Hua Dong; Qin Zhao; Zhi-Ying Li; Yong-Hong Lai; Xiao-Long Cui (Antonie van Leeuwenhoek, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Association of Endothelin-converting Enzyme-1b C-338A Polymorphism with Increased Risk of Ischemic Stroke in Chinese Han Population - Rui Li; Min Cui; Jin Zhao; Mingming Yu; Zegang Ying; Shiming Zhou; Huadong Zhou (Journal of Molecular Neuroscience, 2013)

Up-regulation of SGTB is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Maohong Cao; Wei Xu; Jian Yu; Heyi Zheng; Xiang Tan; Lei Li; Ying Rui; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Tao Tao; et al. (Journal of Molecular Histology, 2013)

Up-regulated expression of Bnip3L after intracerebral hemorrhage in adult rats - Ying Rui; Kaifu Ke; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Guangwei Zhao; Yilu Gao; Maohong Cao (Journal of Molecular Histology, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Increased Expression of Small Heat Shock Protein αB-crystallin After Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Lei Li; Ying Rui; Heyi Zheng; Xiang Tan; Wei Xu; Jianhua Cao; Jian Xu; Gang Cui; Guangfei Xu; Maohong Cao (Journal of Molecular Neuroscience, 2013)

Cardiovascular Toxicity of Different Sizes Amorphous Silica Nanoparticles in Rats After Intratracheal Instillation - Zhongjun Du; Dali Zhao; Li Jing; Guanqun Cui; Minghua Jin; Yang Li; Xiaomei Liu; Ying Liu; Haiying Du; Caixia Guo; Xianqing Zhou; Zhiwei Sun (Cardiovascular Toxicology, 2013)

Genomic sequence analysis of a new reassortant infectious bursal disease virus from commercial broiler flocks in central China - Pei Cui; Shi-Jie Ma; Yu-Geng Zhang; Xin-Sheng Li; Xiao-Yun Gao; Bao-An Cui; Hong-Ying Chen (Archives of Virology, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Small interfering RNA targeting Rac1 sensitizes colon cancer to dihydroartemisinin-induced cell cycle arrest and inhibited cell migration by suppressing NFκB activity - Peng Han; Ying Luan; Yanlong Liu; Zhiwei Yu; Jingwen Li; Zicheng Sun; Gang Chen; Binbin Cui (Molecular and Cellular Biochemistry, 2013)

Effects of urbanization on arable land requirements in China, based on food consumption patterns - Guilin Li; Ying Zhao; Shenghui Cui (Food Security, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

Upregulation of CBLL1 in rat brain cortex after lipopolysaccharide treated - Maohong Cao; Heyi Zheng; Xiang Tan; Wei Xu; Ying Rui; Lei Li; Xiaofei Liu; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Kaifu Ke; et al. (Journal of Molecular Histology, 2013)

Two new oleanane-type saponins from the husks of Xanthoceras sorbifolia Bunge - Ying-Ying Li; Zheng Xiang; Hao Cui; Hang Xiao; Ting-Guo Kang; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2013)

Syntheses and antiproliferative activity of some sulfated hydroximinosterols - Yanmin Huang; Jianguo Cui; Ying Li; Lei Fan; Yanxiao Jiao; Shaoyang Su (Medicinal Chemistry Research, 2013)

Targeted blockade of interleukin-8 abrogates its promotion of cervical cancer growth and metastasis - Suhui Wu; Haixia Shang; Lihuan Cui; Zheng Zhang; Yanli Zhang; Ying Li; Jun Wu; Ren-Ke Li; Jun Xie (Molecular and Cellular Biochemistry, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

Signal-purity-spectrum-based colored deconvolution - Guo-Fa Li; Geng-Xin Peng; Ying Yue; Wan-Li Wang; Yong-Fu Cui (Applied Geophysics, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

Pathology of urethral fibromuscular system related to parturition-induced stress urinary incontinence and TGF-β1/Smad pathway - Guang-Yong Li; Wan-Shou Cui; Feng Zhou; Zhe-Zhu Gao; Hua Xin; Tao Liu; Wei-Ren Li; Yan-Qing Gong; Guang-Yi Bai; Ying-Lu Guo; Zhong-Cheng Xin (Molecular and Cellular Biochemistry, 2012)

A comparative study of the characteristics of two Coxsackie A virus type 16 strains (genotype B) - ErXia Yang; Heng Zhao; Ying Zhang; JianSheng Liu; Yun Liao; LiChun Wang; PingFang Cui; LiXian Yang; LongDing Liu; ChengHong Dong; ShaoZhong Dong; CongWen Shao; et al. (Science China Life Sciences, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Molecular cloning, expression, sequence analyses of dust mite allergen Der f 6 and its IgE-binding reactivity with mite allergic asthma patients in southeast China - Yubao Cui; Ying Zhou; Weihong Shi; Guifang Ma; Li Yang; Yungang Wang; Li Li (Molecular Biology Reports, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Estimation of water dynamics in a vertical-flow constructed wetland with a growing plant species - Ying Ouyang; Shi Ming Luo; Li Hua Cui; Ying Hu Liu; Zhong Qin (Journal of Soils and Sediments, 2010)

Improving Cellular Properties for Genetic Manipulation by Dispersed Growing Mutagenesis in Myxococcus fulvus HW-1 - Cui-ying Zhang; Ke Cai; Zhi-hong Wu; Yue-zhong Li (Current Microbiology, 2010)

Regulatory effects of insulin-like growth factor-1 on the expression of sensory neuropeptide mRNAs in cultured dorsal root ganglion neurons with excitotoxicity induced by glutamate - Hui-Cui Gong; Xiang-Dong Yang; Zhen Liu; Zi-Ying Xing; Huai-Jing Wang; Zhen-Zhong Li (Neuroscience Bulletin, 2010)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Plane wave shot PSDM and controlled illumination techniques - Xingfu Cui; Hongbing Li; Ying Hu; Guibao Liu; Shukai Chen (Applied Geophysics, 2007)

Wavefield continuation datuming using a near surface model - Xingfu Cui; Hongbing Li; Ying Hu; Hong Liang; Li Qi (Applied Geophysics, 2007)

Epoxypropane biosynthesis by Methylomonas sp. GYJ3: batch and continuous studies - Jia-Ying Xin; Jun-Ru Cui; Li-Min Zhu; Jian-Bo Chen; Chun-Gu Xia; Shu-Ben Li (World Journal of Microbiology and Biotechnology, 2002)